Granular water-absorbing agent and method for producing the same
By adding nitrogen atom chelating agent and sulfur atom inorganic reducing agent upstream of the polymerization process of the water-absorbing resin, the problems of poor addition effect and tone stability of the chelating agent are solved, and the uniform distribution and high residue rate of the chelating agent are achieved, and the performance of the water-absorbing resin is improved.
Patent Information
- Application Number
- CN202080078727.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-12
- Filing Date
- 2020-11-12
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2040-11-12
AI Technical Summary
In the prior art, when adding a chelating agent to a water-absorbing resin, it is difficult to obtain sufficient effects that match the added amount, and decomposition of the chelating agent leads to deterioration of the color tone, affecting the tone stability of the water-absorbing resin.
By adding a chelating agent with nitrogen atoms and an inorganic reducing agent with sulfur atoms upstream of the polymerization process, the chelating agent ratio is controlled to be in the range of 0.8 to 1.8, so as to achieve uniform distribution of the chelating agent and the reduction of decomposition.
The uniform distribution and high residue of the chelating agent are achieved, and the tone stability of the water-absorbing resin is improved and the effect of preventing urine deterioration is prevented.
Smart Images

Figure BDA0003639964140000421 
Figure BDA0003639964140000431 
Figure BDA0003639964140000441
Abstract
Description
Technical Field
[0001] The present invention relates to a granular water-absorbing agent and a method for producing the same. Background Art
[0002] Super absorbent polymer (SAP) is a water-swellable, water-insoluble polymer gelling agent. It is used as absorbent articles such as diapers and sanitary napkins, as well as water-retaining agents for agriculture, forestry and horticulture, and industrial waterproofing materials. It is mainly used for disposable purposes.
[0003] This water-absorbent resin is manufactured through a polymerization process, a drying process, a pulverization process, a classification process, a surface cross-linking process, etc. As the main application of disposable diapers becomes more high-performance, various functions are required for the water-absorbent resin. Specifically, it is not limited to a simple high water absorption rate, but also includes gel strength, water absorption rate, water absorption rate under pressure, liquid permeability, antibacterial properties, impact resistance, powder flowability, deodorization, coloration resistance (whiteness), low dust and other properties.
[0004] In order to improve the above-mentioned performance of the water-absorbent resin, additives are sometimes used. For the purpose of improving the color tone stability of the water-absorbent resin, it is known to add a chelating agent to the water-absorbent resin (for example, Patent Documents 1 to 5).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2011 / 040530
[0008] Patent Document 2: International Publication No. 2015 / 053372
[0009] Patent Document 3: Japanese Patent Application Publication No. 2003-206305
[0010] Patent Document 4: Japanese Patent Application Publication No. 2005-029751
[0011] Patent Document 5: International Publication No. 2009 / 005114 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] The present inventors, in the process of conducting research on the addition of chelating agents, found that when a chelating agent is added in an upstream process of a manufacturing process, such as a polymerization process, it is sometimes difficult to obtain a sufficient effect in the final product that matches the amount of the chelating agent added. As the cause of this problem, it was clarified that the water-absorbent resin of the final product does not contain an amount of chelating agent that matches the amount of the chelating agent added in the polymerization process. It was further clarified that the reason why the water-absorbent resin of the final product does not contain a prescribed amount of chelating agent is the decomposition of the chelating agent, and the decomposition product of the chelating agent is one of the reasons for the deterioration of the color tone of the water-absorbent resin of the final product. On the other hand, it was also clarified that if a chelating agent is added downstream of the manufacturing process or the chelating agent is unevenly distributed, the color tone stability of the water-absorbent resin of the final product is insufficient.
[0014] The present invention is made to solve at least one of the above-mentioned problems, and provides a granular water absorbent in which a chelating agent is uniformly distributed and the decomposition products of the chelating agent are small. Alternatively, a granular water absorbent in which a chelating agent is uniformly distributed and appears white is provided. Alternatively, a granular water absorbent in which a chelating agent exerts a desired effect (e.g., color stability, prevention of urine deterioration) is provided. Alternatively, the subject is to provide a method for manufacturing a granular water absorbent in which the chelating agent is added in an upstream process of the manufacturing process, such as a polymerization process, so that the residual rate of the chelating agent in the granular water absorbent as a final product is increased.
[0015] Solutions for solving problems
[0016] The inventors of the present invention have investigated the causes of the above-mentioned problems in order to solve them. As a result, they have found that at least one of the above-mentioned problems can be solved by the constitution of the following particulate water-absorbing agent, thereby completing the present invention. The particulate water-absorbing agent has a poly(meth)acrylic acid (salt)-based water-absorbing resin as a main component, the particulate water-absorbing agent contains a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom, and the chelating agent ratio of the particulate water-absorbing agent calculated according to the following steps (a) to (c) is 0.8 to 1.8, (a) subjecting the particulate water-absorbing agent to a predetermined impact test; (b) using a JIS standard sieve, sieving the particulate water-absorbing agent subjected to the impact test into a particle group 1 having a particle size of less than 300 μm and a particle group 2 having a particle size of 300 μm or more and less than 850 μm; (c) after quantifying the content C1 of the chelating agent present in the particle group 1 and the content C2 of the chelating agent present in the particle group 2, C1 is divided by C2.
[0017] Furthermore, at least one of the above-mentioned problems can be solved by the configuration of a method for producing a particulate water-absorbing agent having a poly(meth)acrylic acid (salt)-based water-absorbing resin as a main component, the particulate water-absorbing agent comprising a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom, the method comprising the step of adjusting the ratio of the chelating agent to 0.8 to 1.8, thereby completing the production method of the present invention.
[0018] Effects of the Invention
[0019] According to one embodiment of the present invention, a granular water absorbent can be provided in which a chelating agent is uniformly distributed and the decomposition products of the chelating agent are small. Alternatively, a granular water absorbent can be provided in which a chelating agent is uniformly distributed and appears white. Alternatively, a granular water absorbent can be provided in which a chelating agent exerts a desired effect (e.g., color stability, prevention of urine deterioration). Alternatively, a method for manufacturing a granular water absorbent can be provided in which a chelating agent is added in an upstream process of a manufacturing process, such as a polymerization process, so that the residual rate of the chelating agent in the granular water absorbent as a final product is increased. DETAILED DESCRIPTION
[0020] Hereinafter, the method for producing a water-absorbent resin containing a chelating agent according to the present invention will be described in detail, but the scope of the present invention is not limited to these descriptions, and in addition to the following examples, appropriate changes and implementations can be made within the scope that does not impair the gist of the present invention. Specifically, the present invention is not limited to the following embodiments, and various changes can be made within the scope indicated by the claims, and embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.
[0021] [1] Various definitions
[0022] [1-1] Water-absorbent resin
[0023] In this specification, the "water-absorbing resin" refers to a polymer gelling agent having a water-swellability (CRC) of 5 g / g or more as specified in ERT441.2-02 and a water-insolubility (Ext) of 50% by mass or less as specified in ERT441.2-02.
[0024] In this specification, "water-absorbent resin" is not limited to the form in which the total amount (100% by mass) is only the water-absorbent resin. It may be a water-absorbent resin composition containing additives, etc. In addition, in this specification, "water-absorbent resin" is a concept that also includes intermediates in the production process of water-absorbent resin. For example, a hydrogel-like cross-linked polymer after polymerization, a dried polymer after drying, a water-absorbent resin powder before surface cross-linking, etc. are sometimes expressed as "water-absorbent resin".
[0025] [1-2] Water absorbent, granular water absorbent
[0026] In this specification, the "water absorbing agent" refers to an absorbent gelling agent containing a water absorbing resin as a main component and used for absorbing an aqueous liquid (liquid). Here, the aqueous liquid (liquid) is not limited to water, as long as it is a liquid containing water.
[0027] In this specification, "granular water absorbent" refers to a granular water absorbent. The concept of "granular water absorbent" includes both a single granular water absorbent and an aggregate of multiple granular water absorbents. In this specification, "granular" means a granular form. Here, "granule" refers to a smaller division of a substance, with a number of The size of the particle is several mm (see "particles", McGraw-Hill Scientific and Technical Terms Dictionary 3rd Edition, compiled by the McGraw-Hill Scientific and Technical Terms Dictionary Editorial Committee, Nikkan Kogyo Shimbun, 1996, p. 1929). It should be noted that in this specification, "particulate water absorbing agent" may be abbreviated as "water absorbing agent".
[0028] The particulate water-absorbing agent contains a water-absorbing resin in the form of a polymer as a main component. The particulate water-absorbing agent contains the water-absorbing resin in the form of a polymer usually in an amount of 50% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more. The remainder of the particulate water-absorbing agent may be a water-absorbing resin composition optionally containing water, additives (inorganic fine particles, etc.), etc.
[0029] The upper limit of the water-absorbing resin in the particulate water-absorbing agent is, for example, 99.999 mass%, 99 mass%, 97 mass%, 95 mass%, or 90 mass%. In addition, it is preferred that the particulate water-absorbing agent further contain 0 to 10 mass% of components, particularly water, additives (inorganic fine particles, polyvalent metal cations), etc., in addition to the water-absorbing resin.
[0030] The particulate water absorbing agent preferably has a water content of 0.2 to 30% by mass. A water absorbing resin composition in which components such as water and additives are integrated with a water absorbing resin is also included in the “particulate water absorbing agent”.
[0031] [1-3] Poly(meth)acrylic acid (salt)
[0032] In this specification, "poly(meth)acrylic acid (salt)" refers to poly(meth)acrylic acid and / or its salt. In addition, poly(meth)acrylic acid (salt)-based resin refers to a polymer that contains repeating units derived from (meth)acrylic acid and / or its salt (hereinafter referred to as "(meth)acrylic acid (salt)") as a main component and also contains a graft component as an optional component. The above-mentioned poly(meth)acrylic acid (salt) is obtained by polymerization of (meth)acrylic acid (salt), hydrolysis of polyacrylamide, polyacrylonitrile, etc. The above-mentioned poly(meth)acrylic acid is preferably obtained by polymerization of (meth)acrylic acid (salt). Here, "containing ** as a main component" means that the amount of acrylic acid (salt) relative to the total amount of monomers used in the polymerization (excluding internal crosslinking agents) is usually 50 to 100 mol%, preferably 70 to 100 mol%, more preferably 90 to 100 mol%, and further preferably substantially 100 mol%.
[0033] [1-4] EDANA and ERT
[0034] "EDANA" is the abbreviation of European Disposables and Nonwovens Associations. "ERT" is the abbreviation of EDANA Recommended Test Methods, a European standard (essentially a world standard) established by EDANA. In this specification, unless otherwise specified, the physical properties of water-absorbent resins are measured in accordance with the 2002 edition of ERT.
[0035] [1-5] Others
[0036] In the present specification, "X to Y" indicating a range means "above X and below Y". In the present specification, unless otherwise specified, "t (ton)" as a mass unit means "metric ton". "ppm" means "mass ppm". "Mass" and "weight", "parts by mass" and "parts by weight", "mass %" and "weight %", "mass ppm" and "weight ppm" are respectively regarded as having the same meaning. In the present specification, "acid (salt)" means "acid (salt)" and / or its salt. "(Meth)acrylic acid" means "acrylic acid and / or methacrylic acid". In the present specification, the unit of volume "liter" is sometimes expressed as "l" or "L". "Mass %" is sometimes expressed as "wt %". When measuring trace components, the detection limit is expressed as ND (Non Detected). In addition, unmeasured is expressed as N / A (Not Available).
[0037] 〔2〕Granular water absorbent
[0038] A particulate water-absorbing agent according to one embodiment of the present invention is a particulate water-absorbing agent having a poly(meth)acrylic acid (salt)-based water-absorbing resin as a main component, the particulate water-absorbing agent comprising a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom, and the chelating agent ratio of the particulate water-absorbing agent calculated according to the following steps (a) to (c) is 0.8 to 1.8. Here, as the steps, (a) a predetermined impact test is performed on the particulate water-absorbing agent; (b) the particulate water-absorbing agent subjected to the impact test is sieved using a JIS standard sieve into a particle group 1 having a particle size of less than 300 μm and a particle group 2 having a particle size of 300 μm or more and less than 850 μm; (c) after quantifying the content C1 of the chelating agent present in the particle group 1 and the content C2 of the chelating agent present in the particle group 2, C1 is divided by C2. It should be noted that the predetermined impact test is based on the method of the [Impact Test] described in the Examples. In the present invention, it is necessary to obtain both the particle group 1 and the particle group 2 by the sieving in the above-mentioned (b), and for this reason, the particulate water-absorbing agent preferably has a particle size described below. In addition, the water-absorbing resin usually has a strength to such an extent that the particle group 2 does not completely disappear in the above-mentioned specified impact test. In addition, regarding the contents C1 and C2 of the chelating agent, when the chelating agent is a nonionic type, it is the original content when added, and when the chelating agent is anionic, it is the content calculated by assuming that the chelating agent exists in the form of an acid in the particulate water-absorbing agent.
[0039] According to one embodiment of the present invention, the lower limit of the chelating agent ratio (C1 / C2) is 0.8 or more, and may be 0.9 or more or 1.0 or more. On the other hand, as an upper limit, it must be 1.8 or less, preferably 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less or 1.1 or less. When the value exceeds 1.8, there is a concern that the hue of the water-absorbent resin cannot be improved. It should be noted that the above-mentioned chelating agent ratio of 0.8 to 1.8 simply means that the chelating agent is uniformly present in the water-absorbent resin. The presence of the chelating agent can also be confirmed by scraping the water-absorbent resin from the surface of the particles of the water-absorbent resin toward the inside of the particles little by little, and analyzing the debris. It should be noted that in this specification, the "prescribed impact test" is based on the method described in the embodiments of the present application.
[0040] [Chelating agent]
[0041] In one embodiment of the present invention, the particulate water absorbing agent contains a chelating agent having a nitrogen atom (hereinafter referred to as "chelating agent" for short). As chelating agents, chelating agents not containing nitrogen atoms are also known, but even if such chelating agents are used, the expected effects of the present invention cannot be achieved.
[0042] In one embodiment of the present invention, the chelating agent is at least one compound selected from the group consisting of amino polycarboxylic acids and amino polyphosphoric acids. It should be noted that the above-mentioned "poly" means that there are multiple functional groups in one molecule, preferably 2 to 30, more preferably 3 to 20, further preferably 4 to 10, and further preferably 5 to 9 functional groups.
[0043] The molecular weight of the chelating agent is preferably 100 to 5,000, more preferably 150 to 1,000, from the viewpoint of the influence on polymerization and the physical properties of the obtained particulate water-absorbing agent.
[0044] Specific examples of the amino polycarboxylic acid include iminodiacetic acid, hydroxyethyliminodiacetic acid, nitrilotriacetic acid, nitrilotripropionic acid, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraaminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, N,N-bis(2-hydroxyethyl)glycine, diaminopropanoltetraacetic acid, ethylenediaminedipropionic acid, N-hydroxyethylethylenediaminetriacetic acid, glycol ether diaminetetraacetic acid, diaminopropanetetraacetic acid, N,N'-bis(2-hydroxybenzyl)ethylenediamine-N,N'-diacetic acid, 1,6-hexamethylenediamine-N,N,N',N'-tetraacetic acid, and salts thereof.
[0045] Specific examples of the aminopolyphosphoric acid include ethylenediamine-N,N'-di(methylenephosphinic acid), ethylenediaminetetra(methylenephosphinic acid), cyclohexanediaminetetra(methylenephosphinic acid), ethylenediamine-N,N'-diacetic acid-N,N'-di(methylenephosphinic acid), ethylenediamine-N,N'-di(methylenephosphinic acid), ethylenediaminetetra(methylenephosphinic acid), polymethylenediaminetetra(methylenephosphinic acid), diethylenetriaminepenta(methylenephosphinic acid) and salts thereof.
[0046] Among these, from the viewpoint of preventing coloration and gel stability, preferably, an amino polycarboxylic acid chelating agent having 4 or more (or 5 or more) carboxyl groups or an amino polyphosphoric acid chelating agent having 4 or more (or 5 or more) phosphonic acid groups is used. In one embodiment of the present invention, from the viewpoint of preventing coloration and gel stability, more preferably, diethylenetriaminepentaacetic acid, nitrilotriacetic acid, triethylenetetraaminehexaacetic acid, ethylenediaminetetrakis (methylenephosphonic acid) and their salts are used. From the viewpoint of preventing coloration and further improving the residual rate of the chelating agent, diethylenetriaminepentaacetic acid or its salt is particularly preferred.
[0047] In one embodiment of the present invention, examples of the salt of the chelating agent include sodium, but are not limited to these.
[0048] It should be noted that, in the present invention, the content and addition amount of the chelating agent described below, unless otherwise specified, are the net content (net content) when added when the chelating agent is nonionic, and are the content calculated as if the chelating agent is in the form of acid when the chelating agent is anionic.
[0049] [Inorganic reducing agent having a sulfur atom]
[0050] As the inorganic reducing agent having a sulfur atom (also referred to as "inorganic reducing agent" in this specification), compounds having a reducing sulfur atom can be cited. In one embodiment of the present invention, the number of sulfur atoms in one molecule of the inorganic reducing agent is 1 to 3, 1 or 2, or 1. From the viewpoint of effectively exerting the desired effect of the present invention, it is preferably 1.
[0051] In one embodiment of the present invention, the inorganic reducing agent may be in an acidic form or a salt form, preferably in a salt form, more preferably a monovalent or polyvalent metal salt, and further preferably a monovalent metal salt. Among them, the oxygen-containing reducing inorganic compound exemplified below, i.e., an inorganic reducing agent formed by bonding sulfur and oxygen, is preferably an oxygen-containing reducing inorganic salt.
[0052] In one embodiment of the present invention, examples of the inorganic reducing agent having a reducing sulfur atom include a +4-valent sulfur compound (e.g., sulfite, bisulfite, or pyrosulfite), a +3-valent sulfur compound (e.g., dithionite), and a +2-valent sulfur compound (e.g., hyposulfite). It should be noted that a sulfur compound having an oxidation number of +6 (positive 6) is the most stable, and generally, each atom having an oxidation number lower than this has reducing properties.
[0053] In one embodiment of the present invention, the inorganic reducing agent having a reducing sulfur atom is not particularly limited, and examples thereof include sulfites such as sodium sulfite, potassium sulfite, calcium sulfite, zinc sulfite, and ammonium sulfite; bisulfites such as sodium bisulfite, potassium bisulfite, calcium bisulfite, and ammonium bisulfite; pyrosulfites such as sodium pyrosulfite, potassium pyrosulfite, and ammonium pyrosulfite; dithionites such as sodium dithionite, potassium dithionite, ammonium dithionite, calcium dithionite, and zinc dithionite; trithionates such as potassium trithionate and sodium trithionate; tetrathionates such as potassium tetrathionate and sodium tetrathionate; and thiosulfates such as sodium thiosulfate, potassium thiosulfate, and ammonium thiosulfate. These inorganic compounds may be in the form of hydrates.
[0054] In one embodiment of the present invention, the inorganic reducing agent is preferably a sulfite or a hydrogensulfite in terms of ease of handling and initial color tone. In one embodiment of the present invention, the salt is preferably an alkali metal or an alkaline earth metal, more preferably a lithium salt, a sodium salt, or a potassium salt, and particularly preferably a sodium salt.
[0055] It should be noted that the description related to "containing a poly(meth)acrylic acid (salt)-based water-absorbing resin as a main component" can be applied to the contents described in the above [1-2], and the method for producing a poly(meth)acrylic acid (salt)-based water-absorbing resin can be applied to the contents described in the later-mentioned [3] method for producing a particulate water-absorbing agent.
[0056] [Particle size of granular water-absorbing agent]
[0057] In one embodiment of the present invention, the mass average particle size (D50) of the particulate water-absorbing agent is preferably 200 to 600 μm, more preferably 200 to 550 μm, and even more preferably 250 to 500 μm.
[0058] In one embodiment of the present invention, in the particulate water absorbing agent, the proportion of particles (microparticles) having a particle size of less than 150 μm is controlled to be less than 5 mass %, less than 3 mass % or less than 1 mass % (the lower limit is 0 mass %). It should be noted that the proportion of particles having a particle size of less than 850 μm is generally 90 to 100 mass %, preferably 95 to 100 mass % relative to the whole. Therefore, the particulate water absorbing agent having a particle size of less than 850 μm used in the determination of the chelating agent ratio of the present invention represents the properties of the particulate water absorbing agent.
[0059] In one embodiment of the present invention, in the particulate water-absorbing agent, the mass ratio of particles having a particle size of less than 300 μm to particles having a particle size of 300 μm or more and less than 850 μm is preferably 70:30 to 10:90, more preferably 60:40 to 15:85, further preferably 50:50 to 20:80, and particularly preferably 40:60 to 25:75. It should be noted that the above-mentioned "particles having a particle size of less than 300 μm" refers to a particulate water-absorbing agent that passes through a JIS standard sieve with a mesh size of 300 μm, and the above-mentioned "particles having a particle size of 300 μm or more and less than 850 μm" refers to a particulate water-absorbing agent that passes through a JIS standard sieve with a mesh size of 850 μm and remains on a JIS standard sieve with a mesh size of 300 μm.
[0060] In one embodiment of the present invention, the proportion of particles having a particle size of 150 μm or more and less than 850 μm as defined by the JIS standard sieve in the particulate water absorbing agent is preferably 90 mass % or more, more preferably 95 mass % or more, and even more preferably 98 mass % or more.
[0061] In one embodiment of the present invention, the logarithmic standard deviation (σζ) of the particle size distribution of the particulate water absorbing agent is preferably controlled to be 0.20 to 0.50, more preferably 0.25 to 0.45, and even more preferably 0.27 to 0.40.
[0062] [Monomer addition ratio]
[0063] In one embodiment of the present invention, the particulate water absorbing agent can be obtained by polymerizing a monomer of a monomer aqueous solution containing a chelating agent having a nitrogen atom to which a chelating agent having a nitrogen atom is added, wherein the amount C3 (relative to the monomer solid content) of the chelating agent added to the monomer aqueous solution is 50% by mass or more relative to the total amount C5 of the chelating agent added in the manufacturing process of the particulate water absorbing agent, and the content C6 of the chelating agent relative to the solid content of the particulate water absorbing agent is 50% by mass or more of C5. In this embodiment, when the chelating agent is added in an upstream process of the manufacturing process, such as a polymerization process, etc., a sufficient effect corresponding to the amount of the chelating agent added can be easily obtained in the final product.
[0064] In this embodiment, the C3 is more preferably 60% by mass or more relative to the C5, and further preferably 70% by mass or more, 80% by mass or more, or 90% by mass or more. By this embodiment, the chelating agent ratio can be in the range of 0.8 to 1.8. In addition, since the polymerization is stable, it is easy to obtain a particulate water-absorbing agent with high physical properties. It should be noted that the C3 is the amount of the chelating agent added relative to the monomer solid content contained in the monomer aqueous solution, and the C5 is the total amount of the chelating agent added in the manufacturing process of the particulate water-absorbing agent converted into the amount of the chelating agent added relative to the solid content of the monomer or water-absorbing resin at each addition. If the "each addition" is explained in detail, the amount of the chelating agent added refers to the amount of the chelating agent added relative to the solid content of the water-absorbing resin or monomer at the time of addition. Regarding the amount of the chelating agent added, when it is added twice to the monomer aqueous solution and the hydrogel in the manufacturing process, it is set to the amount obtained by adding the amount of the chelating agent added relative to the monomer solid content (C3) and the amount of the chelating agent added relative to the hydrogel solid content (C4).
[0065] In this way, the aforementioned C6 is preferably 51% by mass or more of the aforementioned C5, more preferably 52% by mass or more, further preferably 53% by mass or more, further preferably 54% by mass or more, further preferably 55% by mass or more, further preferably 56% by mass or more, further preferably 57% by mass or more, further preferably 58% by mass or more, further preferably 59% by mass or more, further preferably 60% by mass or more, further preferably 61% by mass or more, further preferably 65% by mass or more, further preferably 70% by mass or more, further preferably 75% by mass or more, further preferably 80% by mass or more. By this way, it is easy to obtain a sufficient effect consistent with the addition amount of the chelating agent in the final product. In this way, the aforementioned C6 is, for example, less than 90% by mass, less than 87% by mass or less than 85% by mass of the aforementioned C5.
[0066] [Gel addition ratio]
[0067] In one embodiment of the present invention, the particulate water-absorbing agent is obtained by adding a chelating agent having a nitrogen atom to a hydrogel obtained by polymerizing monomers in an aqueous monomer solution or to a particulate hydrogel obtained by pulverizing the hydrogel, wherein the amount C4 of the chelating agent added to the hydrogel or the particulate hydrogel is 50% by mass or more relative to the total amount C5 of the chelating agent added in the manufacturing process of the particulate water-absorbing agent, and the content C6 of the chelating agent relative to the solid content of the particulate water-absorbing agent is 50% by mass or more of C5. According to this embodiment, when the chelating agent is added in an upstream process of the manufacturing process, such as a polymerization process, etc., it is easy to obtain a sufficient effect in accordance with the amount of the chelating agent added in the final product.
[0068] In this embodiment, the amount of C4 relative to the amount of C5 is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. In this embodiment, the chelating agent ratio can be in the range of 0.8 to 1.8. It should be noted that the amount of C4 is the amount added relative to the solid content of the hydrogel or the granular hydrogel.
[0069] In one embodiment of the present invention, the chelating agent residual rate is more than 50% by mass. By this method, it is easy to obtain a sufficient effect consistent with the addition amount of the chelating agent in the final product. Here, the chelating agent residual rate refers to a value (addition amount C3, addition amount C4 are not particularly limited) that can be calculated by (content C6 / overall amount C5) × 100. In one embodiment of the present invention, the chelating agent residual rate is more than 51% by mass, more than 52% by mass, more than 53% by mass, more than 54% by mass, more than 55% by mass, more than 56% by mass, more than 57% by mass, more than 58% by mass, more than 59% by mass, more than 60% by mass, more than 61% by mass, more than 61% by mass, more than 65% by mass, more than 70% by mass, more than 75% by mass, more than 80% by mass or more than 85% by mass. By this method, it is easy to obtain a sufficient effect consistent with the addition amount of the chelating agent in the final product. In one embodiment of the present invention, the residual chelating agent ratio is 95% by mass or less, 90% by mass or less, 87% by mass or less, or 85% by mass or less. This embodiment provides a technical effect that the initial color tone of the particulate water-absorbing agent is excellent, in other words, white. Alternatively, various technical effects are expected to be produced due to the residual chelating agent.
[0070] It should be noted that, in view of the purpose of the present invention, the particulate water-absorbing agent of the present invention should be defined by the content of the chelating agent decomposition product, but since the chelating agent decomposition product is expected to be a plurality of compounds, it is difficult to identify the compound and measure its content. Therefore, in the present invention, the expression of "product" including the expression of manufacturing process (Product by Process, defining the product by process) (the amount added in the manufacturing process, etc.) is sometimes performed.
[0071] In one embodiment of the present invention, the content (content ratio) C7 (mass ppm) of the chelating agent remaining in the particulate water-absorbing agent is 10 to 5000 ppm, 100 to 5000 ppm, 200 to 3000 ppm or 500 to 2000 ppm. This embodiment has the effect of preventing coloration over time and preventing urine deterioration.
[0072] In one embodiment of the present invention, the content C6 is 10 to 5000 ppm, more preferably 100 to 5000 ppm, further preferably 200 to 3000 ppm, further preferably 500 to 2000 ppm relative to the solid content (mass) of the particulate water absorbing agent. This embodiment has the effect of preventing coloration over time and preventing urine deterioration.
[0073] In one embodiment of the present invention, the chelating agent in the water-absorbing resin or the chelating agent in the particulate water-absorbing agent is quantified by the method described in Examples.
[0074] [Inorganic reducing agent concentration]
[0075] In one embodiment of the present invention, the content (content ratio) of the inorganic reducing agent remaining in the particulate water-absorbing agent is preferably 1 to 3000 ppm, more preferably 10 to 3000 ppm, and even more preferably 12 to 2000 ppm. In this embodiment, the synergistic effect with the chelating agent has the effect of preventing coloration over time and preventing urine deterioration. Here, if it exceeds 3000 ppm, there is a concern that the water-absorbing resin may deteriorate. In one embodiment of the present invention, the content (content rate) of the inorganic reducing agent remaining in the particulate water-absorbing agent is 20 ppm or more, 30 ppm or more, 40 ppm or more, 50 ppm or more, 60 ppm or more, 100 ppm or more, 500 ppm or more, 700 ppm or more, 800 ppm or more, 1000 ppm or more, 1200 ppm or more, 1300 ppm or more, 1500 ppm or more, 2000 ppm or more, 2200 ppm or more, 2300 ppm or more, 2500 ppm or more, 3000 ppm or more, 3200 ppm or more, 3300 ppm or more, 3500 ppm or more, 4000 ppm or more, or 4500 ppm or more. In one embodiment of the present invention, the content (content ratio) of the inorganic reducing agent remaining in the particulate water-absorbing agent is 6000 ppm or less, 5000 ppm or less, 4500 ppm or less, 4000 ppm or less, 3500 ppm or less, 3000 ppm or less, 2500 ppm or less, 2000 ppm or less, 1500 ppm or less, 1000 ppm or less, 500 ppm or less, or 100 ppm or less. By having such a lower limit or upper limit, the desired effect of the present invention can be effectively exerted.
[0076] [Content (Ratio) of Residual Monomers in Particulate Water-Absorbing Agent]
[0077] In one embodiment of the present invention, the content of residual monomers in the above-mentioned particulate water-absorbing agent is 1000ppm or less. In this way, even if the particulate water-absorbing agent is used in sanitary materials, low skin irritation can be expected. In one embodiment of the present invention, the content (mass) of residual monomers in the above-mentioned particulate water-absorbing agent is preferably 700ppm or less, more preferably 500ppm or less, and further preferably 300ppm or less. As the lower limit of the residual monomers, it is sufficient to be about 1ppm. It should be noted that, regardless of the neutralization rate, it is regarded as the presence of unneutralized acrylic acid to obtain the content.
[0078] [Initial color tone of granular water absorbent]
[0079] In one embodiment of the present invention, the particulate water absorbing agent has a poly(meth)acrylic acid (salt)-based water absorbing resin as a main component, the particulate water absorbing agent contains a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom, and the initial color tone of the particulate water absorbing agent is preferably 88 or more, more preferably 88.7 or more, further preferably 89 or more, and further preferably 90 or more in the Hunter Lab color system. The upper limit is 100, but in reality, it is, for example, 97 or less or 95 or less.
[0080] In one embodiment of the present invention, the particulate water-absorbing agent containing a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom and having a poly(meth)acrylic acid (salt)-based water-absorbing resin as a main component has an a value in the Hunter Lab color system of preferably -3 to 3, more preferably -2 to 2, and even more preferably -1 to 1. Furthermore, the b value is preferably 0 to 6, more preferably 0 to 5, even more preferably 0 to 4, even more preferably 0 to 3, even more preferably 0 to 2, and even more preferably 0 to 1.
[0081] In one embodiment of the present invention, the particulate water-absorbing agent comprising a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom and having a poly(meth)acrylic acid (salt)-based water-absorbing resin as a main component preferably has a yellowness (YI) of 12 or less, 11 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6.5 or less, 6 or less, 5 or less, 4 or less, 3 or less, and 2 or less in the Hunter Lab color system, in that order.
[0082] It should be noted that, as the L value approaches 100, the whiteness increases, and as the a value, b value, and yellowness approach 0, the coloration decreases, and the color appears substantially white.
[0083] [Particle shape of particulate water-absorbing agent]
[0084] In one embodiment of the present invention, the particle shape of the particulate water absorbent is an irregular crushed shape. By adopting this method, there is a technical effect that the particulate water absorbent is easy to observe because of the complex reflection of light and also presents a white brilliance visually. Here, the irregular crushed shape refers to crushed particles with an irregular shape. The particulate water absorbent described in one embodiment of the present invention is preferably a crushed product obtained by aqueous solution polymerization. On the other hand, when not undergoing a crushing process, representatively, spherical particles or granules of spherical particles obtained by reverse suspension polymerization, spray droplet polymerization such as spraying or dripping and polymerizing the polymerization monomer, etc. are not irregular crushed shapes. In one embodiment of the present invention, the average roundness of the particulate water absorbent is preferably less than 0.83, more preferably less than 0.80, and further preferably less than 0.75. In the case of aggregates, the average roundness of the primary particles is within the above range.
[0085] The calculation method of the average circularity is as follows. Randomly select more than 100 particulate water absorbents, use an electron microscope (Keyence Corporation, VE-9800) (magnification 50 times) to photograph each particulate water absorbent, obtain an image of the particulate water absorbent, and use the attached image analysis software to calculate the perimeter and area of each particle. In the case of aggregates, the primary particles on the front side that are easy to observe are also evaluated in the same way. The circularity of each particle is calculated using the following formula, and the average value of the obtained values is calculated as the average circularity.
[0086] [Mathematical formula 1]
[0087] Roundness = 4 × π × area / (circumference) 2
[0088] In one embodiment of the present invention, the CRC in the particulate water-absorbing agent is preferably 35 g / g or more, more preferably 39 g / g or more, further preferably 40 g / g or more, and particularly preferably 41 g / g or more. In particular, by being 41 g / g or more, it is possible to achieve both the conventionally contradictory properties of preventing urine degradation and high water absorption rate. In one embodiment of the present invention, the CRC in the particulate water-absorbing agent may be 60 g / g or less or 50 g / g or less.
[0089] In one embodiment of the present invention, the AAP (defined in ERT 442.2-02) in the particulate water absorbing agent is preferably 10 g / g or more, more preferably 15 g / g or more, and even more preferably 20 g / g or more. In one embodiment of the present invention, the AAP in the particulate water absorbing agent may be 40 g / g or less or 35 g / g or less.
[0090] [Various additives]
[0091] In one embodiment of the present invention, the particulate water absorbing agent contains various additives. In this embodiment, a desired function can be imparted to the particulate water absorbing agent. In one embodiment of the present invention, the various additives include, for example, the following additives.
[0092] Examples include: water-insoluble inorganic fine particles (e.g., metal oxides such as silicon dioxide, titanium oxide, zinc oxide, and aluminum oxide; silicates (salts) such as calcium phosphate, natural zeolite, and synthetic zeolite; kaolin, talc, clay, bentonite, hydrotalcite, and aluminum hydroxide); water-soluble deodorants (e.g., extracts from leaves of plants of the family Theaceae, and other known substances); polyvalent metal salts (e.g., containing metals selected from Mg, Ca, Ti, Zr, V, Cr, Mn, Co, Ni, Pd, Cu, Zn, Cd, Organic acid salt or inorganic acid salt of at least one metal (polymetallic cation) in Al, specifically, aluminum sulfate, aluminum lactate, polyaluminum chloride, magnesium sulfate, zirconium sulfate, etc.); antibacterial agents, fragrances, foaming agents, pigments, dyes, plasticizers, adhesives, surfactants, fertilizers, oxidants, salts, bactericides; hydrophilic polymers such as polyethylene glycol and polyethyleneimine; hydrophobic polymers such as alkanes; thermoplastic resins such as polyethylene and polypropylene; thermosetting resins such as polyester resins and urea resins, etc.
[0093] In one embodiment of the present invention, the timing for adding various additives is not particularly limited, and may be, for example, the polymerization step, gel pulverization step, drying step, pulverization step, classification step, surface crosslinking step, or one or more between the steps.
[0094] In one embodiment of the present invention, in the process of producing the particulate water-absorbing agent, a reducing agent (e.g., sulfite, bisulfite) is added in the drying process or thereafter in order to reduce residual monomers. As such, in one embodiment of the present invention, in the process of producing the particulate water-absorbing agent, a step of adding an inorganic reducing agent having a sulfur atom to the hydrogel or particulate hydrogel and a step of adding a reducing agent (e.g., sulfite, bisulfite) in the drying process or thereafter can be used in combination.
[0095] In one embodiment of the present invention, with respect to the particulate water-absorbing agent, it is preferred to add the aforementioned water-insoluble inorganic fine particles having a volume average particle size of 0.2 to 3 μm to the particle surface of the particulate water-absorbing agent. Thus, there is a technical effect of improving the initial color tone. The type of the aforementioned water-insoluble inorganic fine particles is not limited as long as it is a white powder, and it is preferably selected from one or more of titanium oxide, aluminum oxide, calcium phosphate, hydrotalcite or aluminum hydroxide. The volume average particle size of the aforementioned water-insoluble inorganic fine particles is more preferably 0.3 to 2 μm, and further preferably 0.4 to 1.5 μm. It should be noted that the aforementioned volume average particle size is measured using a "laser diffraction scattering method" (using, for example, a particle size analyzer manufactured by Nikkiso Co., Ltd., trade name: MICROTRAC MT3000II). In addition, the actual presence of the aforementioned water-insoluble inorganic fine particles on the particle surface of the particulate water-absorbing agent can be confirmed by magnifying it to 5000 times with an electron microscope and observing it. It should be noted that, from the viewpoint of improving the initial color tone, it is preferred that the particle size of the water-insoluble inorganic fine particles is larger than the particle size (particle size of about several tens of nanometers) of fumed silica (e.g., AEROSIL (trademark)) commonly used in the prior art as described above. In addition, the content of the water-insoluble inorganic fine particles is preferably 0.1 to 1% by mass, more preferably 0.2 to 0.8% by mass, relative to the particulate water-absorbing agent.
[0096] [3] Method for producing granular water-absorbing agent
[0097] In one embodiment of the present invention, there is provided a method for producing a particulate water-absorbing agent, which has a poly(meth)acrylic acid (salt)-based water-absorbing resin as a main component, the particulate water-absorbing agent contains a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom, and the production method has a step of making the ratio of the chelating agent 0.8 to 1.8. According to this embodiment, by adding the chelating agent in an upstream process of the production process, such as a polymerization process, the residual rate of the chelating agent in the particulate water-absorbing agent as a final product can be increased. It should be noted that regarding the "step of making the ratio of the chelating agent 0.8 to 1.8", the description in the specification (especially the above description) applies. In addition, the "main component" has the same meaning as that described in [1-3] polyacrylic acid (salt).
[0098] In one embodiment of the present invention, there is provided a method for producing a particulate water-absorbing agent, the method comprising the steps of: preparing a monomer aqueous solution containing (meth)acrylic acid (salt) and persulfate (salt); polymerizing the monomer contained in the monomer aqueous solution to obtain a hydrogel; grinding the hydrogel as required to obtain a particulate hydrogel; drying the hydrogel or the particulate hydrogel to obtain a dry polymer; grinding or classifying the dry polymer to obtain a water-absorbing resin powder; and surface crosslinking the water-absorbing resin powder to obtain water-absorbing resin particles, wherein the particulate hydrogel is subjected to surface crosslinking. The method for producing a water-absorbing agent comprises the following steps: (i) adding the aforementioned chelating agent in an amount of 10 to 5000 ppm (monomer mass basis) of the monomer components to the aforementioned monomer aqueous solution, and / or, (ii) adding the aforementioned chelating agent in an amount of 10 to 5000 ppm of the solid content (mass) of the hydrogel or the aforementioned granular hydrogel to the aforementioned hydrogel or the aforementioned granular hydrogel, and the method for producing a granular water-absorbing agent comprises the following steps: (iii) adding an inorganic reducing agent having a sulfur atom in an amount of 10 to 50000 ppm of the solid content (mass) of the hydrogel or the aforementioned granular hydrogel to the aforementioned hydrogel or the aforementioned granular hydrogel. Each step is described in detail below. In one embodiment of the present invention, from the viewpoint of further improving the residual rate of the chelating agent, it is also preferred to use the steps (i) and (ii) in combination.
[0099] [Step of Preparing Monomer Aqueous Solution]
[0100] This step is a step of preparing a monomer aqueous solution containing (meth)acrylic acid (salt) and persulfate (salt).
[0101] In one embodiment of the present invention, (meth)acrylic acid (salt) contains a polymerization inhibitor. As the above-mentioned polymerization inhibitor, phenols can be preferably listed, methoxyphenols can be more preferably listed, and p-methoxyphenol is further preferably listed. From the viewpoint of the effect of inhibiting polymerization and the color tone of the obtained water-absorbing resin or particulate water-absorbing agent, the concentration is preferably 10 to 200 ppm, and more preferably 10 to 100 ppm. It should be noted that it is preferred that a part or all of the above-mentioned polymerization inhibitor also remains in the particulate water-absorbing agent as the final product.
[0102] In one embodiment of the present invention, (meth)acrylic acid is partially or completely neutralized. As the alkaline substance used at this time, for example, alkali metal carbonate (bicarbonate), alkali metal hydroxide, ammonia, organic amine, etc. can be cited. From the viewpoint of obtaining a water-absorbing resin or a particulate water-absorbing agent with higher physical properties, it is preferably an alkali metal hydroxide such as sodium hydroxide, potassium hydroxide, lithium hydroxide, and more preferably sodium hydroxide. More specifically, for example, a monomer aqueous solution containing (meth)acrylic acid is mixed with an alkaline substance. In one embodiment of the present invention, the neutralization rate of (meth)acrylic acid (salt) is preferably 10 to 90 mol%, more preferably 40 to 85 mol%, further preferably 50 to 80 mol%, and particularly preferably 60 to 75 mol%. It should be noted that the aforementioned neutralization rate can also be applied to the neutralization rate of the particulate water-absorbing agent as the final product. Therefore, in the case where (meth)acrylic acid is not neutralized or is polymerized at a neutralization rate lower than the aforementioned neutralization rate, the water-containing gel-like cross-linked polymer can also be neutralized.
[0103] In one embodiment of the present invention, the monomer concentration in the aforementioned monomer aqueous solution is preferably 10 to 80% by mass, more preferably 20 to 75% by mass, and further preferably 30 to 70% by mass. In addition, in one embodiment of the present invention, as a preferred example of aqueous solution polymerization described later, high concentration polymerization in which the monomer concentration in the aforementioned monomer aqueous solution is made into a high concentration can be cited. The monomer concentration in the aforementioned monomer aqueous solution in high concentration polymerization is preferably 30% by mass or more, more preferably 35% by mass or more, and further preferably 39% by mass or more (the upper limit is the saturation concentration). By this method, there is a technical effect that the drying process can be labor-saving and the chelating agent residual rate can be improved. In one embodiment of the present invention, high concentration polymerization and high temperature start polymerization described later can be used in combination.
[0104] In one embodiment of the present invention, a monomer aqueous solution containing (meth) acrylic acid is mixed with an internal crosslinking agent. As an internal crosslinking agent, a compound having two or more substituents capable of reacting with (meth) acrylic acid can be cited. Specifically, one or more of the internal crosslinking agents described in column 14 of U.S. Patent No. 6241928 can be used. In one embodiment of the present invention, as an internal crosslinking agent, a compound having two or more polymerizable unsaturated groups is preferably used. In addition, in one embodiment of the present invention, as an internal crosslinking agent, a water-soluble compound capable of dissolving more than 1% by mass in water at 25°C is preferably used. By this method, the water absorption performance of the obtained water-absorbing resin or particulate water-absorbing agent is improved. In one embodiment of the present invention, the amount of the internal crosslinking agent is preferably 0.001 to 2 mol%, more preferably 0.005 to 1 mol%, and further preferably 0.01 to 0.5 mol% relative to the monomer. According to this method, the desired water absorption characteristics can be efficiently obtained.
[0105] In one embodiment of the present invention, 10 to 5000 ppm (monomer mass basis) of the chelating agent is added to the aqueous monomer solution. Preferably, 100 to 5000 ppm, 200 to 4000 ppm, 300 to 3800 ppm, 400 to 3500 ppm, 500 to 3000 ppm, 600 to 2500 ppm, 700 to 2000 ppm, 800 to 1900 ppm, 860 to 1800 ppm, 870 to 1,700 ppm or 900 to 1,650 ppm of the chelating agent is added to the aqueous monomer solution. In other words, in one embodiment of the present invention, the aqueous monomer solution contains the chelating agent in the above range. According to this embodiment, there is a technical effect of stabilizing polymerization. Extremely small amounts of transition metal ions contained in substances such as iron ions and copper ions dissolved from water, raw materials, and polymerization containers may be the cause of delaying the start of polymerization and rapid polymerization. The above effect is obtained by allowing the chelating agent to capture iron ions and copper ions.
[0106] In one embodiment of the present invention, the aqueous monomer solution contains 800 ppm or more, 860 ppm or more, 870 ppm or more, 900 ppm or more, 1000 ppm or more, 1200 ppm or more, 1400 ppm or more, 1600 ppm or more, 1800 ppm or more, 2000 ppm or more, 2200 ppm or more, 2500 ppm or more, or 3000 ppm or more of the chelating agent based on the mass of the monomer. In one embodiment of the present invention, the aqueous monomer solution contains 5000 ppm or less, 4000 ppm or less, 3800 ppm or less, 3500 ppm or less, 3000 ppm or less, or 2500 ppm or less of the chelating agent based on the mass of the monomer.
[0107] In one embodiment of the present invention, when diethylenetriaminepentaacetic acid or a salt thereof is added as the chelating agent to the aqueous monomer solution, 2500 ppm or less of diethylenetriaminepentaacetic acid or a salt thereof is added.
[0108] In one embodiment of the present invention, if the aforementioned aqueous monomer solution is mixed with an alkaline substance, for example, for neutralizing acrylic acid as a monomer, the temperature of the mixed solution can be 40°C to the boiling point or 50°C to the boiling point due to the action of at least one of the heat of neutralization and the heat of dissolution. In this embodiment, for example, at 40°C to the boiling point or 50 to 102°C, it is mixed with persulfate (salt) as a polymerization initiator. According to this embodiment, the following technical effects are achieved: the evaporation of water in the polymerization can be promoted, the drying process can be labor-saving, and the residual rate of the chelating agent is improved. In one embodiment of the present invention, as persulfate, suitable ones are, for example, sodium persulfate, potassium persulfate, ammonium persulfate, etc.
[0109] In one embodiment of the present invention, the amount of persulfate (salt) is preferably 0.01 mol% or more, more preferably more than 0.015 mol%, more preferably 0.02 mol% or more, further preferably 0.03 mol% or more, and further preferably 0.04 mol% or more relative to the aforementioned monomer. If the amount of persulfate (salt) is less than 0.01 mol% relative to the aforementioned monomer, there is a concern that the residual monomer becomes more. Alternatively, there is a concern that the desired effect of the present invention cannot be effectively exerted. In one embodiment of the present invention, the amount of persulfate (salt) is preferably 0.5 mol% or less, more preferably 0.2 mol% or less, and further preferably 0.15 mol% or less relative to the aforementioned monomer. According to this method, there is a technical effect of improving the residual rate of the chelating agent.
[0110] It should be noted that, as the polymerization initiator, in addition to the above-mentioned persulfate, a photoinitiator, an azo initiator or hydrogen peroxide can be used, and a reducing agent can be used as a redox initiator. It should be noted that the reducing agent added in the preparation step of the monomer aqueous solution is usually completely consumed in the polymerization step, so even if an inorganic reducing agent having a sulfur atom is used as the reducing agent, the subject of the present invention cannot be solved.
[0111] In one embodiment of the present invention, the aqueous monomer solution may contain other monomers in addition to (meth)acrylic acid. Examples of the other monomers include water-soluble or hydrophobic unsaturated monomers. Specifically, one or more of the monomers described in paragraph
[0035] of U.S. Patent Application Publication No. 2005 / 215734 (excluding (meth)acrylic acid) are used depending on the purpose.
[0112] In one embodiment of the present invention, in addition to the above-mentioned substances, the following substances may be added to the aforementioned monomer aqueous solution. Specifically, water-soluble resins or water-absorbent resins other than poly(meth)acrylic acid (salt), various foaming agents (such as carbonates, azo compounds, bubbles, etc.), surfactants, chain transfer agents, etc. may be listed. According to this embodiment, the various physical properties of the obtained water-absorbent resin or particulate water-absorbent agent can be improved. In this embodiment, the upper limit of the amount of water-soluble resins or water-absorbent resins other than poly(meth)acrylic acid (salt) is preferably 50% by mass or less, more preferably 20% by mass or less in the aforementioned monomer aqueous solution. In this embodiment, the upper limit of the amount of foaming agents (such as carbonates, azo compounds, bubbles, etc.), surfactants, chain transfer agents, etc. is 5% by mass or less, more preferably 1% by mass or less in the aforementioned monomer aqueous solution. According to this embodiment, the various physical properties of the obtained water-absorbent resin or particulate water-absorbent agent can be improved. In one embodiment of the present invention, the use of a water-soluble resin or a water-absorbent resin other than poly(meth)acrylic acid (salt) provides a graft polymer or a water-absorbent resin composition (e.g., starch-acrylic acid polymer, PVA-acrylic acid polymer, etc.), but in the present invention, these polymers and water-absorbent resin compositions are also referred to as polyacrylic acid (salt)-based water-absorbent resins.
[0113] [Polymerization process]
[0114] This step is a step of polymerizing the monomers contained in the aqueous monomer solution to obtain a hydrogel-like crosslinked polymer (hereinafter also referred to as "hydrogel").
[0115] In one embodiment of the present invention, the polymerization method is preferably spray droplet polymerization in a gas phase, aqueous solution polymerization, or reversed phase suspension polymerization in a hydrophobic solvent, more preferably aqueous solution polymerization or reversed phase suspension polymerization, further preferably aqueous solution polymerization, and particularly preferably continuous aqueous solution polymerization. This method makes it easy to control the polymerization, and the water absorption properties of the obtained water-absorbent resin are improved.
[0116] In one embodiment of the present invention, as a preferred example of aqueous solution polymerization, high temperature start polymerization can be listed. In one embodiment of the present invention, the lower limit of the polymerization start temperature of high temperature start polymerization can be 40°C or more. In one embodiment of the present invention, it is preferably 50°C or more, more preferably 60°C or more, and further preferably 70°C or more. By this method, the polymerization time can be shortened and the chelating agent residual rate can be increased.
[0117] In one embodiment of the present invention, the upper limit of the polymerization initiation temperature for high-temperature polymerization initiation is preferably equal to or lower than the boiling point, and more preferably equal to or lower than 100° C. or equal to or lower than 90° C. According to this embodiment, there is a technical effect of stabilizing polymerization.
[0118] In one embodiment of the present invention, the polymerization start temperature of the polymerization is 40 to 100°C. According to this embodiment, the chelating agent residual rate can be increased. It should be noted that in this specification, the polymerization start temperature is defined as the time when the temperature starts to rise due to polymerization heat. For example, in Example 1, the polymerization start temperature is 95°C.
[0119] In one embodiment of the present invention, the polymerization time in the polymerization process is preferably less than 30 minutes, more preferably less than 15 minutes, and further preferably less than 10 minutes. According to this embodiment, the chelating agent residual rate can be improved. In one embodiment of the present invention, the polymerization time in the polymerization process is preferably more than 10 seconds, more preferably more than 20 seconds, and further preferably more than 30 seconds. According to this embodiment, there is a technical effect of easy control of polymerization. It should be noted that in this specification, the polymerization time is defined as the following time: the temperature rise due to the polymerization heat is taken as the starting point, and the faster one of taking out from the polymerization container or starting drying (excluding the evaporation of water caused by the polymerization heat) is taken as the end point.
[0120] In one embodiment of the present invention, the polymerization process can be carried out in an air atmosphere or in an inert gas atmosphere such as nitrogen or argon. When carried out in an inert gas atmosphere such as nitrogen or argon, the oxygen concentration is preferably controlled to be less than 1% by volume. Regarding the dissolved oxygen in the monomer or the monomer aqueous solution, it is also preferred to fully replace it with an inert gas in advance (for example, the dissolved oxygen is less than 1 (mg / l)). In one embodiment of the present invention, it is also possible to set it as a foaming polymerization in which bubbles (especially the above-mentioned inert gas, etc.) and various foaming agents (especially carbonates) are dispersed in the above-mentioned monomer aqueous solution and polymerized.
[0121] [Gel crushing process]
[0122] The production method according to one embodiment of the present invention preferably includes a gel grinding step.
[0123] This step is a step of pulverizing the hydrogel obtained in the above-mentioned polymerization step to obtain a granular hydrogel. The pulverization method in the gel pulverization step is not particularly limited, and a gel pulverizer such as a kneader, a meat grinder or a cutting mill is suitable. In one embodiment of the present invention, the gel pulverization is preferably applied by the gel pulverization method described in International Publication No. 2011 / 126079.
[0124] In one embodiment of the present invention, the step of adding 10 to 5000 ppm of the chelating agent to the hydrogel or the granular hydrogel, based on the solid content (mass) of the hydrogel or the granular hydrogel, is included. In one embodiment of the present invention, the step of adding 100 to 5000 ppm, 200 to 4000 ppm, 300 to 3800 ppm, 400 to 3500 ppm, 500 to 3000 ppm, 500 to 2000 ppm, 600 to 1900 ppm, 700 to 1850 ppm, 800 to 1800 ppm, 860 to 1800 ppm, 870 to 1,700 ppm, or 900 to 1,650 ppm of the chelating agent to the hydrogel or the granular hydrogel, based on the solid content (mass) of the hydrogel or the granular hydrogel, is included. According to this embodiment, there is a technical effect of increasing the residual rate of the chelating agent. However, compared with the case where the chelating agent is added to the aqueous monomer solution, the distribution of the chelating agent tends to become non-uniform, and C1 / C2 tends to approach the upper limit of 1.8.
[0125] In one embodiment of the present invention, the chelating agent that can be added to the hydrogel or the particulate hydrogel is preferably in the form of an aqueous solution of 0.01 to 20% by mass, more preferably in the form of an aqueous solution of 0.01 to 10% by mass, and still more preferably in the form of an aqueous solution of 0.1 to 5% by mass or 0.1 to 1% by mass, based on the original content at the time of addition when the chelating agent is nonionic, and in the form of anionic, based on the concentration calculated as if the chelating agent is present in the form of an acid in the particulate water-absorbing agent. According to this embodiment, the desired range of the chelating agent ratio of the present invention can be set.
[0126] One embodiment of the present invention includes the step of adding 10 to 50,000 ppm of an inorganic reducing agent having a sulfur atom to the hydrogel or the granular hydrogel, based on the solid content (mass) of the hydrogel or the granular hydrogel. This embodiment may be the step of adding 100 to 50,000 ppm of the inorganic reducing agent having a sulfur atom.
[0127] In one embodiment of the present invention, the amount of the hydrogel or the particulate hydrogel added is 200 to 50000 ppm, 300 to 48000 ppm, 400 to 47000 ppm, 500 to 46000 ppm, 520 to 46000 ppm, 550 to 45500 ppm, 600 to 45000 ppm, 700 to 44000 ppm, 900 to 42000 ppm, 1000 to 40000 ppm, 1100 to 39000 ppm, 2000 to 38000 ppm, 2200 to 37500 ppm, 2500 to 37000 ppm, 3000 to 36000 ppm, 3200 to 35800 ppm, 4500 to 3 5,600ppm, 4000~35400ppm, 4100~35400ppm, 5000~35000ppm, 5200~35000ppm, 5 500~35000ppm, 6000~35000ppm, 6200~35000ppm, 7000~34000ppm, 7500~30000pp m, 8000~30000ppm, 9000~25000ppm, 9500~23000ppm, 10500~23000ppm, 12000~23 000ppm, 13500~23000ppm, 15000~23000ppm, 15000~23000ppm or 18000~22000ppm. According to this embodiment, there is a technical effect of improving the chelating agent residual rate and the initial color tone.
[0128] In one embodiment of the present invention, the inorganic reducing agent having a sulfur atom added to the hydrogel or the granular hydrogel is preferably in the form of a 0.01 to 30% by mass aqueous solution, more preferably in the form of a 0.01 to 20% by mass aqueous solution, further preferably in the form of a 0.02 to 20% by mass aqueous solution, and may be in the form of a 0.03 to 10% by mass aqueous solution, or may be in the form of a 0.03 to 5% by mass aqueous solution. According to this embodiment, there is a technical effect of increasing the residual rate of the chelating agent. In one embodiment of the present invention, the inorganic reducing agent having a sulfur atom added to the hydrogel or the granular hydrogel is in the form of an aqueous solution of 0.5 mass %, 0.9 mass %, 1.0 mass %, 1.5 mass %, 1.8 mass %, 2.2 mass %, 2.5 mass %, 3 mass %, 3.5 mass %, 4.5 mass %, 5 mass %, 5.5 mass %, 6 mass %, 6.5 mass %, 7 mass %, or 7.5 mass %. In one embodiment of the present invention, the inorganic reducing agent having a sulfur atom added to the hydrogel or the granular hydrogel is in the form of an aqueous solution of 30 mass %, 20 mass %, 15 mass %, less than 10 mass %, 9 mass % or 8.5 mass %. According to this embodiment, there is a technical effect of improving the residual rate of the chelating agent.
[0129] In one embodiment of the present invention, the inorganic reducing agent is added while the hydrogel is being crushed. Here, "simultaneously" does not mean that the moment when the hydrogel starts to be crushed and the moment when the inorganic reducing agent is added must be the same, but means that the inorganic reducing agent is mixed in while the hydrogel is being crushed. The time for crushing and the time for adding can be partially overlapped. According to this embodiment, there is a technical effect of increasing the residual rate of the chelating agent.
[0130] In one embodiment of the present invention, the chelating agent is added while the hydrogel is being crushed. This embodiment also means that the chelating agent is mixed into the hydrogel while the hydrogel is being crushed. The crushing time and the adding time can be partially overlapped. According to this embodiment, there is a technical effect of increasing the residual rate of the chelating agent.
[0131] [Drying process]
[0132] This step is a step of drying the aforementioned hydrogel or the aforementioned granular hydrogel to obtain a dry polymer. In one embodiment of the present invention, the aforementioned hydrogel or the aforementioned granular hydrogel is dried until the desired resin solid content is obtained to obtain a dry polymer. The resin solid content is a value obtained by loss on drying (mass change when 1 g of a sample is heated at 180° C. for 3 hours), and is preferably 80% by mass or more, more preferably 85 to 99% by mass, further preferably 90 to 98% by mass, and particularly preferably 92 to 97% by mass.
[0133] In one embodiment of the present invention, the drying method is a method capable of drying the hydrogel or the particulate hydrogel until the resin solid content is reached. In one embodiment of the present invention, examples of the drying method include heating drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum drying, azeotropic dehydration drying with a hydrophobic organic solvent, or high humidity drying using high temperature steam. The drying step may be performed using one drying method. The drying step may be performed using two appropriately selected drying methods.
[0134] In one embodiment of the present invention, among the above-mentioned drying methods, hot air drying is preferred from the viewpoint of drying efficiency. In one embodiment of the present invention, belt drying in which hot air drying is performed on a belt is more preferred. In one embodiment of the present invention, the above-mentioned drying is preferably drying based on hot air at 120 to 250° C., more preferably drying based on hot air at 140 to 220° C., and further preferably drying based on hot air at 160 to 200° C. According to this embodiment, the drying time can be shortened, and there is a technical effect of increasing the residual rate of the chelating agent.
[0135] In one embodiment of the present invention, the drying time is preferably 120 minutes or less, more preferably 80 minutes or less, and further preferably 60 minutes or less. According to this embodiment, there is a technical effect of improving the initial color tone. In one embodiment of the present invention, the drying time is actually 1 minute or more, 3 minutes or more, and further 5 minutes or more.
[0136] In one embodiment of the present invention, in the aforementioned drying, the drying time until the solid content becomes 80% by mass is preferably less than 30 minutes, more preferably less than 20 minutes, and further preferably less than 15 minutes. According to this method, there is a technical effect of improving the residual rate of chelating agent. In one embodiment of the present invention, the drying time until the solid content becomes 80% by mass is actually more than 1 minute, more than 3 minutes.
[0137] In one embodiment of the present invention, when belt drying is performed, it is preferable to apply belt drying conditions described in International Publication No. 2006 / 100300, International Publication No. 2011 / 025012, International Publication No. 2011 / 025013, International Publication No. 2011 / 111657, etc.
[0138] In one embodiment of the present invention, the drying is performed using a dryer selected from a stationary dryer and a belt dryer. This embodiment has a technical effect that drying can be performed in a short time even in mass production.
[0139] In one embodiment of the present invention, the layer height of the aforementioned hydrogel or the aforementioned granular hydrogel stacked in the aforementioned dryer is 1 to 10 cm. If the layer height of the granular hydrogel is too high, there is a concern that the residual rate of the chelating agent will decrease. In one embodiment of the present invention, the layer height of the aforementioned hydrogel or the aforementioned granular hydrogel stacked in the aforementioned dryer is 2 to 6 cm. This method can increase the residual rate of the chelating agent. In one embodiment of the present invention, the layer height of the aforementioned hydrogel or the aforementioned granular hydrogel stacked in the aforementioned dryer is less than 11 cm, less than 10 cm, less than 6 cm, less than 5 cm, less than 4.5 cm or less than 4 cm. In one embodiment of the present invention, the layer height of the aforementioned hydrogel or the aforementioned granular hydrogel stacked in the aforementioned dryer is more than 1 cm or more than 2 cm. It should be noted that the layer height of the hydrogel or particulate hydrogel refers to the value obtained by randomly measuring the layer height of the hydrogel or particulate hydrogel to be stacked at 5 or more points and averaging the values in the case of intermittent drying, and the value obtained by averaging the values obtained by measuring the gel layer height at 5 points at equal intervals in the cross section cut along the direction perpendicular to the forward direction of the drying belt at the location where the stacking is completed in the case of continuous belt drying, and then repeating the measurements every several seconds. As a measuring device, for example, a laser distance meter, a laser displacement meter, etc. can be used for measurement.
[0140] In addition, as a method for setting a desired layer height, for example, a method of adjusting a belt speed when conveying the hydrous gel or the particulate hydrous gel to a dryer by a belt is suitable, but the method is not limited to this.
[0141] In one embodiment of the present invention, the time from the time of adding the inorganic reducing agent to the start of drying is 120 minutes or less, less than 120 minutes, 100 minutes or less, 80 minutes or less, 60 minutes or less, 45 minutes or less, or 30 minutes or less, or the temperature of the hydrogel from the time of adding the inorganic reducing agent to the start of drying is 0 to 55°C. This embodiment can suppress deterioration and coloring caused by the inorganic reducing agent. In this embodiment, the time from the time of adding the inorganic reducing agent to the start of drying is preferably 20 minutes or less, more preferably 10 minutes or less. In this embodiment, the time from the time of adding the inorganic reducing agent to the start of drying is preferably 1 minute or more, more preferably 3 minutes or more. In addition, in this embodiment, the temperature of the hydrogel or particulate hydrogel is preferably 0 to 60°C, more preferably more than 0°C and less than 60°C, and can be 40 to 50°C. The above-mentioned embodiment means that the temperature of the hydrogel or particulate hydrogel is maintained at 0 to 55° C. by heat-retaining means or the like during the period from the time of adding the inorganic reducing agent to the start of drying.
[0142] [Crushing process and classification process]
[0143] This step is a step of pulverizing or classifying the dry polymer to obtain a water-absorbent resin powder. In one embodiment of the present invention, this step is a step of pulverizing the dry polymer obtained in the above-mentioned drying step (pulverization step), adjusting the particle size to a predetermined range (classification step), and obtaining a water-absorbent resin powder (for convenience, the powdered water-absorbent resin before surface cross-linking is referred to as "water-absorbent resin powder").
[0144] In one embodiment of the present invention, the equipment used in the pulverizing step includes, for example, a high-speed rotary pulverizer such as a roller mill, a hammer mill, a screw mill, a pin mill, a vibration mill, a knuckle type pulverizer, a cylindrical agitator, etc. These can be used in combination as needed.
[0145] In one embodiment of the present invention, examples of methods for adjusting the particle size in the classification step include sieve classification using a JIS standard sieve (JIS Z8801-1 (2000)), air flow classification, etc. It should be noted that the particle size adjustment of the water-absorbent resin is not limited to the above-mentioned pulverization step and classification step, and can be appropriately carried out in the polymerization step (particularly reversed phase suspension polymerization, spray droplet polymerization) or other steps (for example, granulation step).
[0146] In one embodiment of the present invention, the weight average particle size (D50) of the water-absorbent resin powder is controlled to preferably 200 to 600 μm, more preferably 200 to 550 μm, and even more preferably 250 to 500 μm.
[0147] In one embodiment of the present invention, the ratio of particles having a particle size of 850 μm or more (coarse particles) is preferably controlled to 5 mass % or less, more preferably 3 mass % or less, and even more preferably 1 mass % or less (the lower limit is 0 mass %).
[0148] In one embodiment of the present invention, the proportion of particles having a particle size of less than 850 μm is preferably 90 to 100% by mass, more preferably 95 to 100% by mass, based on the entirety.
[0149] In the present invention, generally, it is better when the number of particles (microparticles) with a particle size of less than 150 μm contained in the particulate water-absorbing agent is small as described above, but the microparticles sometimes contain a chelating agent at a high concentration. Therefore, instead of removing the microparticles in the aforementioned classification process, a process (granulation process) in which the microparticles are aggregated with other particles to form large particles may be provided in the surface cross-linking process and thereafter. In addition, when removing the microparticles in the aforementioned classification process, a fine powder granulation process in which the microparticles are aggregated with each other to form large particles may be provided. The preferred fine powder granulation process can apply the methods described in U.S. Patent No. 7153910 (micropowder granulation using warm water) and U.S. Patent No. 8598254 (micropowder granulation using water and water vapor). In one embodiment of the present invention, for a substance (water-absorbent resin powder) obtained by pulverizing a dry polymer, particles (microparticles) with a particle size of less than 150 μm are not removed. Alternatively, the proportion of particles (microparticles) with a particle size of less than 150 μm in the particulate water-absorbing agent may be 0.1% by mass or more, 0.3% by mass or more, or 0.5% by mass or more.
[0150] The above particle sizes are measured using JIS standard sieves according to the measurement methods described in U.S. Patent No. 7638570 and EDANA ERT420.2-02. In addition, the above particle sizes can also be applied to the water-absorbing resin after surface crosslinking (hereinafter referred to as "water-absorbing resin particles" for convenience). Therefore, it is preferred to perform surface crosslinking in a manner that maintains the above particle sizes.
[0151] [Surface cross-linking process]
[0152] This step is a step of obtaining water-absorbent resin particles by surface crosslinking the water-absorbent resin powder. In one embodiment of the present invention, this step is a step of forming a portion with a high crosslinking density in the surface layer (a portion several tens of μm from the surface of the water-absorbent resin powder) of the water-absorbent resin powder obtained through the above steps, and is preferably composed of the following steps (1) and (2) or (1) to (3). In this surface crosslinking step, a surface-crosslinked water-absorbent resin (water-absorbent resin particles) is obtained by free radical crosslinking, surface polymerization, a crosslinking reaction with a surface crosslinking agent, etc. at the surface layer of the water-absorbent resin powder.
[0153] (1) Mixing process
[0154] In one embodiment of the present invention, the surface crosslinking agent used in the surface crosslinking process is not particularly limited, and various organic or inorganic surface crosslinking agents can be listed, for example. Among them, from the viewpoint of the physical properties of the water-absorbent resin or the particulate water-absorbent agent and the handleability of the surface crosslinking agent, an organic surface crosslinking agent that reacts with a carboxyl group to form a covalent bond is preferred. Specifically, one or more of the surface crosslinking agents described in columns 9 to 10 of U.S. Patent No. 7183456 can be used. In one embodiment of the present invention, the amount of the surface crosslinking agent (the total amount when two or more are used) is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the water-absorbent resin powder. In one embodiment of the present invention, when adding a surface crosslinking agent to the water-absorbent resin powder, water is preferably used, and more preferably added in the form of an aqueous solution. In this case, the amount of water used is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the water-absorbent resin powder. In one embodiment of the present invention, a hydrophilic organic solvent is used in addition to a surface crosslinking agent and water added as needed. The hydrophilic organic solvent is not particularly limited, and is preferably a monoalcohol or diol having 1 to 3 carbon atoms. It should be noted that diol can also be used as a surface crosslinking agent, but if the heating temperature of the heat treatment step described later is lower than 150°C, it can function as a hydrophilic organic solvent. In one embodiment of the present invention, the amount of the hydrophilic organic solvent used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin powder. When two or more types are used, the total amount is used. In one embodiment of the present invention, the method for adding / mixing the surface crosslinking agent is not particularly limited, and it is preferred that: after preparing the surface crosslinking agent and water, a hydrophilic organic solvent or a mixture thereof as a solvent in advance, the water-absorbent resin powder is sprayed or dripped to add and mixed, and spraying and adding and mixing are more preferred. In one embodiment of the present invention, the mixing device used for mixing the surface crosslinking agent and the water-absorbent resin powder is not particularly limited, and preferably, a high-speed stirring mixer is used, and more preferably, a continuous high-speed stirring mixer is used.
[0155] (2) Heat treatment process
[0156] In one embodiment of the present invention, a surface crosslinking reaction occurs by heating the mixture of the surface crosslinking agent and the water-absorbent resin powder, thereby obtaining water-absorbent resin particles whose surfaces are crosslinked. In one embodiment of the present invention, a known dryer is used for the heat treatment, preferably a paddle dryer. The heating temperature (heat medium temperature) at this time is preferably 80 to 250° C., more preferably 100 to 220° C. In addition, the heating time is preferably 1 to 120 minutes, more preferably 5 to 90 minutes, and even more preferably 10 to 60 minutes.
[0157] (3) Cooling process
[0158] In one embodiment of the present invention, a cooling process is provided after the heating process. The surface crosslinking reaction can be stopped by the cooling process. Alternatively, it is easy to transport to a subsequent process. In one embodiment of the present invention, the cooling process can be applied to a device of the same form as the known dryer used in the heating process. The cooling temperature (refrigerant temperature) at this time is preferably 0 to 90°C, more preferably 20 to 85°C, and further preferably 40 to 80°C.
[0159] As described above, a particulate water absorbing agent containing a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom and having a poly(meth)acrylic acid (salt)-based water absorbing resin as a main component can be produced, wherein the predetermined chelating agent ratio in the particulate water absorbing agent is 0.8 to 1.8.
[0160] In one embodiment of the present invention, there is provided a production method, wherein the particulate water absorbing agent is obtained by polymerizing a monomer of a monomer aqueous solution containing a chelating agent having a nitrogen atom, the amount C3 of the chelating agent added to the monomer aqueous solution (relative to the monomer solid content) is 50% by mass or more relative to the total amount C5 of the chelating agent added in the production process of the particulate water absorbing agent, and the content C6 of the chelating agent relative to the solid content of the particulate water absorbing agent is 50% by mass or more of C5. According to this embodiment, in the embodiment in which the chelating agent is added in an upstream process of the production process, such as a polymerization process, the residual rate of the chelating agent in the particulate water absorbing agent as a final product can be increased. It should be noted that the detailed description of this embodiment has been given in [2] the particulate water absorbing agent, and the description is also applicable, so it is omitted here.
[0161] In one embodiment of the present invention, there is provided a production method, wherein the particulate water-absorbing agent is obtained by adding a chelating agent having a nitrogen atom to a hydrogel or a particulate hydrogel obtained by pulverizing the hydrogel, the hydrogel being obtained by polymerizing a monomer in a monomer aqueous solution, wherein the amount C4 of the chelating agent added to the hydrogel or the particulate hydrogel is 50% by mass or more relative to the total amount C5 of the chelating agent added in the production process of the particulate water-absorbing agent, and the content C6 of the chelating agent relative to the solid content of the particulate water-absorbing agent is 50% by mass or more of C5. According to this embodiment, in an embodiment in which the chelating agent is added in an upstream process of the production process, such as a polymerization process, the residual rate of the chelating agent in the particulate water-absorbing agent as a final product can be increased. It should be noted that the detailed description of this embodiment has been given in [2] the particulate water-absorbing agent, and such description is equally applicable and thus omitted here.
[0162] 〔4〕Application of granular water absorbent
[0163] In one embodiment of the present invention, the use of the particulate water absorbing agent or the particulate water absorbing agent obtained by the above-mentioned production method is not particularly limited, but is preferably used in water-absorbing articles such as disposable diapers, sanitary napkins, and incontinence pads.
[0164] [5] Combination of particularly preferred aspects
[0165] Regarding the methods disclosed in this specification, it is needless to say that the individual methods should be considered to disclose all the combinations of the methods. In other words, it can be the basis for legal modification to explain the combination of particularly preferred methods. As shown below, in the specification of this application, at least two methods from (i) to (xi) are provided as a combination of particularly preferred methods.
[0166] (i) In one embodiment of the present invention, the chelating agent is an aminopolycarboxylic acid-based chelating agent having 4 or more (or 5 or more) carboxyl groups or an aminopolyphosphoric acid-based chelating agent having 4 or more (or 5 or more) phosphonic acid groups.
[0167] (ii) In one embodiment of the present invention, the chelating agent is an aminopolycarboxylic acid-based chelating agent having 4 or more (or 5 or more) carboxyl groups or an aminopolyphosphoric acid-based chelating agent having 4 or more (or 5 or more) phosphonic acid groups.
[0168] (iii) In one embodiment of the present invention, the number of sulfur atoms in one molecule of the inorganic reducing agent is 1 to 3, 1 or 2, or 1.
[0169] (iv) In one embodiment of the present invention, the aqueous monomer solution contains 870 ppm or more or 900 ppm or more of the chelating agent based on the mass of the monomers.
[0170] (v) In one embodiment of the present invention, when the aqueous monomer solution contains diethylenetriaminepentaacetic acid or a salt thereof as the chelating agent, the aqueous monomer solution contains 2500 ppm or less of diethylenetriaminepentaacetic acid or a salt thereof.
[0171] (vi) In one embodiment of the present invention, the amount of persulfate (salt) used is 0.02 mol% or more based on the monomer.
[0172] (vii) In one embodiment of the present invention, a step of adding an inorganic reducing agent having a sulfur atom to the hydrogel or the particulate hydrogel is included, and when the amount of C3 relative to the amount of C5 is 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more, the amount added is 600 ppm or more among the above, and when the amount of C4 relative to the amount of C5 is 70% by mass or more, 80% by mass or more, or 90% by mass or more, the amount added is 400 ppm or more among the above.
[0173] (viii) One embodiment of the present invention includes the step of adding an inorganic reducing agent having a sulfur atom to the hydrogel or the particulate hydrogel in an amount of 4000 ppm or more based on the solid content (mass) of the hydrogel or the particulate hydrogel.
[0174] (ix) In one embodiment of the present invention, the inorganic reducing agent having a sulfur atom added to the hydrogel or the particulate hydrogel is in the form of an aqueous solution at 3.5% by mass or more and less than 10% by mass.
[0175] (x) In one embodiment of the present invention, the layer height of the hydrogel or the particulate hydrogel stacked in the dryer is less than 11 cm or less than 6 cm.
[0176] (xi) In one embodiment of the present invention, the time from the time of adding the inorganic reducing agent to the start of drying is 30 minutes or less, or the temperature of the water-containing gel from the time of adding the inorganic reducing agent to the start of drying is 0 to 55°C.
[0177] Example
[0178] Unless otherwise specified, the various physical properties described in the claims and embodiments of the present invention are obtained according to the EDANA method and the following measurement methods at room temperature (20-25°C) and humidity 50RH%. Furthermore, the electrical equipment shown in the embodiments and comparative examples uses a power supply of 200V or 100V, 60Hz. It should be noted that, for convenience, "liter" is sometimes recorded as "L" and "weight %" is recorded as "wt %". In addition, unless otherwise specified, "%" means "mass %".
[0179] [Manufacture of granular water-absorbing agent]
[0180] [Example 1]
[0181] (Step of Preparing Monomer Aqueous Solution)
[0182] In a polypropylene container having a capacity of 1.5 L and an inner diameter of 80 mm, a solution (A) obtained by adding a 10 mass % polyethylene glycol diacrylate (weight average molecular weight; 523) aqueous solution (3.13 g, 0.02 mol % relative to acrylic acid) as an internal crosslinking agent and an aqueous solution (1.32 g) of a sodium salt of diethylenetriamine pentaacetic acid as a chelating agent, and a solution (B) obtained by diluting a 48.5 mass % sodium hydroxide aqueous solution (180.6 g) with deionized water (209.9 g) adjusted to 50° C. were prepared. The solution (A) was stirred with a magnetic stirrer while the solution (B) was added and mixed to prepare a solution (C). It should be noted that the temperature of the solution (C) rose to 101° C. due to the heat of neutralization and heat of solution generated during the mixing process.
[0183] Thereafter, the solution (C) was stirred continuously, and when the temperature of the solution (C) reached 95° C., a 10% by mass sodium persulfate aqueous solution (3.6 g, 0.05 mol % relative to acrylic acid (sodium), 0.12 g / mol) was added to the solution (C) as a polymerization initiator, and stirred for about 3 seconds to prepare a monomer aqueous solution (1). It should be noted that the chelating agent content of the monomer aqueous solution (1) when converted to the acid form, that is, the content of diethylenetriaminepentaacetic acid, was 856 ppm (relative to the monomer).
[0184] (Polymerization process)
[0185] The neutralization rate of the monomer aqueous solution (1) is 73 mol% and the monomer concentration is 43% by mass. Next, the monomer aqueous solution (1) is flowed into a barrel-shaped container in an atmosphere-open system. It should be noted that the barrel-shaped container is a container with a bottom size of 250 mm×250 mm, a top size of 640 mm×640 mm, a height of 50 mm, a trapezoidal central cross-section, and a Teflon (registered trademark) sheet attached to the inner surface. In addition, the barrel-shaped container is placed on a heating plate heated to 100°C and preheated. After the monomer aqueous solution (1) is flowed into the barrel-shaped container, the polymerization reaction starts after about 5 seconds, and the monomer aqueous solution heats up. The polymerization start temperature is 93°C. After the monomer aqueous solution (1) generates water vapor and expands and foams in all directions upward, the resulting water-containing gel (1) shrinks to a size slightly larger than the bottom of the barrel-shaped container and ends. It should be noted that the polymerization reaction (expansion and contraction) was completed within about 1 minute, and the state of the hydrogel (1) was maintained in the barrel-shaped container for the next 2 minutes. The hydrogel (1) containing bubbles was obtained by the polymerization reaction. The polymerization time was 3 minutes.
[0186] (Gel crushing process)
[0187] Next, the hydrogel (1) obtained in the above polymerization reaction was divided into 16 equal parts, and the hydrogel was added to a table-top meat chopper (MEAT-CHOPPER TYPE: 12VR-400KSOX, manufactured by Iizuka Industries) having a porous plate, and 25 parts by mass of a 0.04% by mass sodium sulfite aqueous solution at 25° C. was added to the hydrogel to grind the gel. Therefore, the amount of sodium sulfite added was 100 ppm based on the solid content of the hydrogel.
[0188] The weight average particle size (D50) of the granular hydrogel (1) obtained in the above gel pulverization was 1.2 mm.
[0189] (Drying process)
[0190] Next, 450 g of the granular hydrogel (1) was spread on a metal net with a mesh size of 300 μm (50 mesh) and placed in a static drying machine. At this time, the layer height of the granular hydrogel stacked in the static drying machine (ventilated airflow intermittent drying machine 71-S6 model (manufactured by Satake Chemical Industry Co., Ltd.)) was measured at 5 locations and the average was 3 cm.
[0191] On the other hand, the timing of adding the inorganic reducing agent in the gel pulverization step was determined in advance, and 180°C hot air ventilation was started 5 minutes after the addition of the inorganic reducing agent. The temperature of the water-containing gel immediately after the gel pulverization was confirmed to be 50°C.
[0192] In the same drying, by repeatedly taking out the semi-dried product from the dryer and measuring the mass, it was found that the solid content reached 80% by mass in 10 minutes.
[0193] After 30 minutes had passed since the start of the hot air ventilation, the hot air ventilation was terminated to obtain a granular dry polymer (1). At this time, the dry polymer had a solid content of 95% by mass.
[0194] (Crushing and classification process)
[0195] Next, the dried polymer (1) was put into a roll mill (WML type roll mill, manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified by a ro-tap sieve classifier using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm, thereby obtaining an irregularly shaped crushed water-absorbent resin (1).
[0196] (Surface cross-linking process)
[0197] Next, a surface crosslinking agent solution (1) containing ethylene glycol diglycidyl ether (0.05 parts by mass), propylene glycol (1 part by mass), deionized water (3.0 parts by mass) and isopropyl alcohol (1 part by mass) was added to the irregularly shaped crushed water-absorbent resin (1) (100 parts by mass) and mixed with a spatula until uniform, thereby obtaining a wetted mixture (1). Next, the wetted mixture (1) was uniformly poured into a stainless steel container (9 cm in diameter and about 1 cm in height), and heated at 180°C for 40 minutes to obtain a surface-crosslinked water-absorbent resin (1).
[0198] Thereafter, the surface-crosslinked water-absorbing resin (1) was passed through a JIS standard sieve having a mesh size of 850 μm to obtain a particulate water-absorbing agent (1) as a final product. The results are shown in the following table.
[0199] [Example 2]
[0200] A particulate water-absorbing agent (2) was produced in the same manner as in Example 1 except that the concentration of the sodium sulfite aqueous solution was 0.2 mass % and the amount of sodium sulfite added was 500 ppm relative to the solid content of the hydrogel. The results are shown in the following table.
[0201] [Example 3]
[0202] A particulate water-absorbing agent (3) was produced in the same manner as in Example 1 except that the concentration of the sodium sulfite aqueous solution was 0.8 mass % and the amount of sodium sulfite added was 2000 ppm relative to the solid content of the hydrogel. The results are shown in the following table.
[0203] [Example 4]
[0204] A particulate water-absorbing agent (4) was produced in the same manner as in Example 1 except that the concentration of the sodium sulfite aqueous solution was 2.0 mass % and the amount of sodium sulfite added was 5000 ppm based on the solid content of the hydrogel. The results are shown in the following table.
[0205] [Example 5]
[0206] In Example 1, the addition amount of sodium salt of diethylenetriaminepentaacetic acid to the aqueous monomer solution (1) was changed to 43 ppm (relative to the monomer) in acid form, the concentration of the aqueous sodium sulfite solution was set to 0.2 mass %, the addition amount of sodium sulfite to the solid content of the hydrogel was changed to 500 ppm, and further, 813 ppm (relative to the solid content of the hydrogel) of sodium salt of diethylenetriaminepentaacetic acid in acid form was added to the aqueous sodium sulfite solution to perform the gel pulverization step, and a particulate water-absorbing agent (5) was produced in the same manner as in Example 1. The results are shown in the following table.
[0207] [Example 6]
[0208] A particulate water-absorbing agent (6) was produced in the same manner as in Example 5 except that the classification was not performed using a JIS standard sieve having an opening of 150 μm. The results are shown in the following table.
[0209] [Example 7]
[0210] A particulate water-absorbing agent (7) was produced in the same manner as in Example 5 except that the concentration of the sodium sulfite aqueous solution was 2.4 mass % and the amount of sodium sulfite added relative to the solid content of the hydrogel was changed to 6000 ppm. The results are shown in the following table.
[0211] [Example 8]
[0212] A particulate water-absorbing agent (8) was produced in the same manner as in Example 6 except that the classification was not performed using a JIS standard sieve having an opening of 150 μm in Example 7. The results are shown in the following table.
[0213] [Example 9]
[0214] In Example 1, the addition amount of the sodium persulfate aqueous solution to the sodium acrylate was changed to 0.055 mol% (0.13 g / mol), the polymerization start temperature was changed to 77°C, the mass of the polymerization raw material was doubled for polymerization, 100 ppm of sodium sulfite was added to the hydrogel relative to the solid content of the hydrogel, the concentration of the sodium hydrogen sulfite aqueous solution was changed to 4 mass%, 10000 ppm of sodium hydrogen sulfite was added relative to the solid content of the hydrogel, and 1 kg of the granular hydrogel was layered and dried. A particulate water-absorbing agent (9) was produced in the same manner as in Example 1. The results are shown in the following table. It should be noted that the gel layer height of the granular hydrogel was 5 cm.
[0215] [Example 10]
[0216] A particulate water-absorbing agent (10) was produced in the same manner as in Example 9 except that the concentration of the sodium hydrogen sulfite aqueous solution was 8 mass % and the amount of sodium hydrogen sulfite added was 20000 ppm relative to the solid content of the hydrogel. The results are shown in the following table.
[0217] [Example 11]
[0218] In Example 9, a particulate water-absorbing agent (11) was produced in the same manner as in Example 9 except that 856 ppm of sodium salt of diethylenetriaminepentaacetic acid in acid form was added, 1910 ppm of ethylenediaminetetraacetic acid was added, the concentration of the sodium hydrogen sulfite aqueous solution was changed to 1.2 mass %, and the amount of sodium hydrogen sulfite added was changed to 3000 ppm relative to the solid content of the hydrogel. The results are shown in the following table.
[0219] [Example 12]
[0220] A particulate water absorbing agent (12) was produced in the same manner as in Example 11 except that 1910 ppm of ethylenediaminetetraacetic acid was added relative to acrylic acid and 1250 ppm of nitrilotriacetic acid was added. The results are shown in the following table.
[0221] [Example 13]
[0222] A particulate water-absorbing agent (13) was produced in the same manner as in Example 11 except that 1910 ppm of ethylenediaminetetraacetic acid and 799 ppm of sodium salt of ethylenediaminetetramethylenephosphonic acid in acid form were added. The results are shown in the following table.
[0223] [Example 14]
[0224] In Example 1, the concentration of the sodium sulfite aqueous solution was set to 1.2% by mass, the amount of sodium sulfite added relative to the solid content of the hydrogel was changed to 6000 ppm, the time from the addition of the inorganic reducing agent to the start of hot air ventilation was changed to 120 minutes, and the particulate hydrogel from the addition of the inorganic reducing agent to the start of drying was placed in a bag so that the water would not evaporate and kept in a windless oven at 60°C. A particulate water-absorbing agent (14) was produced in the same manner as in Example 1. The results are shown in the following table. It should be noted that only Example 14 was subjected to the aging step, and in the other Examples and Comparative Examples (including Examples 21 to 41 described later), the time from the time of adding the inorganic reducing agent to the start of drying was carried out within a period of 5 to 30 minutes.
[0225] [Example 15]
[0226] A particulate water-absorbing agent (15) was produced in the same manner as in Example 1 except that 100 ppm of sodium sulfite was added to the hydrogel relative to the solid content of the hydrogel, the concentration of the sodium thiosulfate pentahydrate aqueous solution was changed to 4.7% by mass, and 11800 ppm of sodium thiosulfate pentahydrate was added to the hydrogel relative to the solid content of the hydrogel. The results are shown in the following table.
[0227] [Example 16]
[0228] A particulate water-absorbing agent (16) was produced in the same manner as in Example 2 except that the amount of sodium persulfate aqueous solution added relative to sodium acrylate was changed to 0.015 mol% (0.04 g / mol). The results are shown in the following table.
[0229] [Example 17]
[0230] A particulate water-absorbing agent (17) was produced in the same manner as in Example 16 except that the concentration of the sodium sulfite aqueous solution was 2.4 mass % and the amount of sodium sulfite added relative to the solid content of the hydrogel was changed to 6000 ppm. The results are shown in the following table.
[0231] [Example 18]
[0232] A particulate water-absorbing agent (18) was produced in the same manner as in Example 1 except that the layer height of the particulate hydrogel during drying was changed to 6 cm. The results are shown in the following table.
[0233] [Example 19]
[0234] A particulate water-absorbing agent (19) was produced in the same manner as in Example 18 except that the layer height of the particulate hydrogel during drying was 11 cm. The results are shown in the following table.
[0235] [Example 20]
[0236] In Example 1, the addition amount of deionized water to the hydrogel was changed to 6 g relative to the solid content of the hydrogel, the concentration of the sodium sulfite aqueous solution was set to 10% by mass, and the addition amount of sodium sulfite to the solid content of the hydrogel was changed to 6000 ppm, and a particulate water-absorbing agent (20) was produced in the same manner as in Example 1. The results are shown in the following table.
[0237] [Comparative Example 1]
[0238] A comparative particulate water-absorbing agent (1) was produced in the same manner as in Example 1 except that sodium sulfite was not added. The results are shown in the following table.
[0239] [Comparative Example 2]
[0240] A comparative particulate water-absorbing agent (2) was produced according to Examples 1 to 7 described in International Publication No. 2011 / 040530. The results are shown in the following table.
[0241] [Comparative Example 3]
[0242] A comparative particulate water-absorbing agent (3) was produced according to Example 6 described in International Publication No. 2015 / 053372. The results are shown in the following table.
[0243] [Comparative Example 4]
[0244] A comparative particulate water-absorbing agent (4) was produced according to Example 1 described in Japanese Patent Application Laid-Open No. 2003-206305. The results are shown in the following table.
[0245] [Comparative Example 5]
[0246] A comparative particulate water-absorbing agent (5) was produced according to Example 2 described in Japanese Patent Application Laid-Open No. 2003-206305. The results are shown in the following table.
[0247] [Comparative Example 6]
[0248] A comparative particulate water-absorbing agent (6) was produced in the same manner as in Example 1 except that 100 ppm of sodium sulfite and 6000 ppm of oxalic acid dihydrate were added relative to the solid content of the hydrogel. The results are shown in the following table.
[0249] [Comparative Example 7]
[0250] In Example 5, the sodium salt of diethylenetriaminepentaacetic acid was not added to the hydrogel, and in the surface crosslinking step, 0.0813 parts by mass of the sodium salt of diethylenetriaminepentaacetic acid in acid form was added to the surface crosslinking agent solution (1), and the deionized water was changed to 2.9 parts by mass of the surface crosslinking agent solution (2), and the mixture was added to 100 parts by mass of the irregularly shaped crushed water-absorbent resin. A comparative particulate water-absorbing agent (7) was produced in the same manner as in Example 5. The results are shown in the following table.
[0251] 〔Various measurements〕
[0252] [Solid content of water-absorbent resin]
[0253] The ratio of the non-volatile components in the water-absorbent resin at 180° C. is expressed as the solid content. The relationship between the solid content and the water content is as follows.
[0254] Solid content (mass %) = 100 - water content (mass %)
[0255] The method for measuring the solid content is as follows. About 1 g of water-absorbing resin (mass W1) is weighed into an aluminum cup (mass W0) with a bottom diameter of about 5 cm, and the mixture is dried in a windless dryer at 180°C for 3 hours. The mass (W2) of the "aluminum cup + water-absorbing resin" after drying is measured, and the solid content is calculated using the following formula.
[0256] Solid content (mass %) = ((W2-W0) / W1) × 100
[0257] In addition, about the block-like dry polymer, 5 samples were collected from various positions, crushed so that the particle size might be 5 nm or less, and then measured, and the average value was adopted.
[0258] [Solid content of hydrogel]
[0259] The solid content of the particulate hydrogel was measured by the same method as the above-mentioned "Solid content of water-absorbent resin", except that the amount of hydrogel was changed to about 2 g, the drying temperature was changed to 180° C., and the drying time was changed to 24 hours.
[0260] [Residual monomers]
[0261] The residual monomers were measured according to the EDANA method (ERT410.2-02).
[0262] [Chelating agent content, residual amount and residual rate]
[0263] The chelating agent in the particulate water absorbing agent was extracted and analyzed by the method described in International Publication No. 2015 / 053372.
[0264] Specifically, 1 g of the particulate water-absorbing agent obtained in each example and comparative example was added to 100 g of a 0.9 mass % sodium chloride aqueous solution and stirred at room temperature for 1 hour (stirring speed: 500 ± 50 rpm) to extract the chelating agent into the 0.9 mass % sodium chloride aqueous solution. Thereafter, the swollen gel was filtered using filter paper (No. 2 / retention particle size specified in JIS P3801; 5 μm / manufactured by Toyo Filter Paper Co., Ltd.). Next, the resulting filtrate was passed through a filter for HPLC sample pretreatment (chromatographic disk 25A / water type, pore size; 0.45 μm / manufactured by Kurabo Industries Co., Ltd.), and the content of the chelating agent in the filtrate was determined using high performance liquid chromatography (HPLC). The content of the chelating agent in the particulate water-absorbing agent was determined by taking into account the dilution rate of the particulate water-absorbing agent relative to the 0.9 mass % sodium chloride aqueous solution using a calibration curve obtained by measuring a chelating agent standard solution of known concentration as an external standard. Furthermore, the HPLC measurement conditions are appropriately changed according to the type of chelating agent. Specifically, for diethylenetriaminepentaacetic acid (DTPA), ethylenediaminetetraacetic acid (EDTA) and nitrilotriacetic acid (NTA), the quantitative determination is performed according to the following measurement condition 1, and for ethylenediaminetetra(methylenephosphonic acid) (EDTMP), the quantitative determination is performed according to the following measurement condition 2.
[0265] Measurement condition 1:
[0266] <Eluent>: A mixed solution of 0.3 ml of 0.4 mol / L alum aqueous solution, 450 ml of 0.1 N potassium hydroxide aqueous solution, 3 ml of 0.4 mol / L tetra-n-butylammonium hydroxide aqueous solution, 3 ml of sulfuric acid, 1.5 ml of ethylene glycol and 2550 ml of ion exchange water
[0267] <Column>: LichroCART 250-4 Superspher 100RP-18e (4 μm) (Merck)
[0268] <Column temperature>: 23±2℃
[0269] <Flow rate>: 1ml / min
[0270] <Detector>: UV, wavelength 258nm.
[0271] Measurement condition 2:
[0272] <Eluent>: 0.003 mol / L sulfuric acid aqueous solution
[0273] <Column>: Shodex IC NI-424 (manufactured by Showa Denko K.K.)
[0274] <Column temperature>: 40°C
[0275] <Flow rate>: 1ml / min
[0276] <Detector>: RI.
[0277] The content of the above-mentioned chelating agent is affected by the water content. Therefore, the content C6 of the chelating agent of the present invention is a value corrected for the water content and is a value converted relative to the solid content of the particulate water absorbent. The contents C1, C2, and C7 of the chelating agent of the present invention are values that are not corrected for the water content. When the chelating agent is anionic, it is regarded as existing in the form of acid in the water-absorbing resin and the particulate water absorbent. The standard curve is prepared using the added chelating agent standard solution and converted to the acid by calculation using the molecular weight.
[0278] [Inorganic reducing agent concentration]
[0279] The inorganic reducing agent in the particulate water absorbing agent was extracted and analyzed by the method described in International Publication No. 2011 / 040530.
[0280] Specifically, 50g of ion exchange water and 0.5g of water-absorbent resin were added to a 200ml beaker and allowed to stand for 1 hour. Then, after adding 50g of methanol, 2.5g of a solution obtained by dissolving 2mmol of malachite green in the eluent described later was added. After stirring the solution for about 30 minutes, it was filtered and the filtrate was analyzed by high performance liquid chromatography to determine the amount of reducing agent contained in the particulate water absorbent. In addition, the eluent was adjusted in a ratio of 400ml of methanol, 6ml of n-hexane, and 100ml of sodium salt of 0.0M-2-N-morpholinoethanesulfonic acid. In addition, a standard curve was prepared by analyzing the substance obtained by adding a reducing agent to a particulate water absorbent without a reducing agent. The detection limit of the inorganic reducing agent based on the above analysis is 5ppm.
[0281] [Coloring Evaluation]
[0282] The evaluation of the initial color tone of the water-absorbent resin was performed using a spectrophotometer SZ-Σ80 COLOR MEASURING SYSTEM manufactured by Nippon Denshoku Industries. As for the setting conditions for the measurement, reflection measurement was selected, and an attached powder / paste sample stand with an inner diameter of 30 mm and a height of 12 mm was used. As a standard, a standard round white plate No. 2 for powder / paste was used, and a 30Φ projection tube was used. About 5 g of the granular water-absorbing agent obtained in the examples and comparative examples was added to the equipped sample stand. The filling was a state in which the equipped sample stand was filled to about 60%. Under the conditions of room temperature (20 to 25°C) and humidity 50RH%, the L value (Lightness: brightness index) and YI value (yellowness; yellowness index) in the Hunter Lab color system of the surface were measured using the above-mentioned spectrophotometer. A higher L value is better, and the smaller the YI value, the lower the coloration and the closer it is to white. Using the same measurement method using the same device, the a and b values (chromaticity) of the object color of other scales can also be measured simultaneously. The smaller the a and b values are, the lower the coloration is and the closer to white it is.
[0283] [Coloring promotion test]
[0284] The coloring acceleration test of the water-absorbent resin was conducted by placing the powder / paste sample stand containing about 5 g of the water-absorbent resin used in the evaluation of the initial color tone in a constant temperature and humidity chamber adjusted to 70°C and 65% humidity for 7 days. The color tone after the coloring acceleration test was measured by placing the powder / paste sample stand placed in the constant temperature and humidity chamber directly in a spectrophotometer with the same color tone as the initial color tone and using the same measurement conditions.
[0285] [Impact test]
[0286] 30 g of the particulate water absorbent obtained in each embodiment and comparative example and 10 g of glass beads with a diameter of 6 mm were placed in a glass container (diameter 6 cm, height 11 cm), and the particulate water absorbent was crushed using a paint stirrer (product No. 488 test disperser / manufactured by Toyo Seiki Seisakusho Co., Ltd.). It should be noted that the above crushing was performed by vibrating the paint stirrer at 800 (cycle / min) (CPM) for 30 minutes. After the above vibration, the glass beads were removed using a JIS standard sieve with a mesh size of 2 mm. In addition, the details of the paint stirrer (disperser) are disclosed in Japanese Patent Publication No. 9-235378.
[0287] The particulate water absorbing agent subjected to the above impact test was sieved using a JIS standard sieve into a particle group 1 having a particle size of less than 300 μm and a particle group 2 having a particle size of 300 μm or more and less than 850 μm.
[0288] After the chelating agent content C1 in the particle group 1 and the chelating agent content C2 in the particle group 2 were quantified, C1 was divided by C2 to obtain the chelating agent ratio (C1 / C2). The results are shown in the following table.
[0289] [Table 1]
[0290]
[0291] [Table 2]
[0292]
[0293] [Table 3]
[0294]
[0295] [Table 4]
[0296]
[0297] [Table 5]
[0298]
[0299] [Table 6]
[0300]
[0301] 〔Investigation〕
[0302] In Examples 1 to 6, the chelating agent was added in the upstream process of the production process, but the chelating agent residual rate was good. On the other hand, the chelating agent residual rate of Comparative Example 1 was poor.
[0303] In Examples 1 to 4 and 9 to 20, the particulate water absorbent is obtained by polymerizing the monomers of the monomer aqueous solution containing the chelating agent having a nitrogen atom, and the amount of the chelating agent added C3 (relative to the monomer solid content) contained in the monomer aqueous solution is 50% by mass or more relative to the total amount of the chelating agent added in the manufacturing process of the particulate water absorbent C5. However, it was confirmed that the chelating agent residual rate was 50% or more. In Examples 5 to 8, the particulate water absorbent is obtained by adding the chelating agent having a nitrogen atom to the particulate hydrogel obtained by pulverizing the hydrogel obtained by polymerizing the monomers of the monomer aqueous solution. The amount of the chelating agent added to the particulate hydrogel C4 is 50% by mass or more relative to the total amount of the chelating agent added in the manufacturing process of the particulate water absorbent C5. However, it was confirmed that the chelating agent residual rate exceeded 50%. In summary, it is suggested that a sufficient effect corresponding to the amount of the chelating agent added is obtained in the final product. In addition, the chelating agent ratio was 0.8 to 1.8 in each example.
[0304] On the other hand, in Comparative Example 1 (no reducing agent used) and Comparative Example 6 (using oxalic acid), the particulate water absorbing agent is obtained by polymerizing a monomer of a monomer aqueous solution containing a chelating agent having a nitrogen atom, and the amount of the chelating agent added C3 (relative to the monomer solid content) contained in the monomer aqueous solution is 50% by mass or more relative to the total amount C5 of the chelating agent added in the manufacturing process of the particulate water absorbing agent. As a result, it can be confirmed that the chelating agent residual rate is less than 50%. It is presumed that this is because no inorganic reducing agent having a sulfur atom is added in the manufacturing process of the particulate water absorbing agent.
[0305] In Comparative Example 3, the amount of chelating agent added to the aqueous monomer solution C3 is less than 50% by mass relative to the total amount of chelating agent added in the manufacturing process of the particulate water-absorbing agent C5, and the amount of chelating agent added to the particulate hydrogel C4 is less than 50% by mass relative to the total amount of chelating agent added in the manufacturing process of the particulate water-absorbing agent C5. A large amount of chelating agent having nitrogen atoms is added in the downstream process of the manufacturing process of the particulate water-absorbing agent, so the chelating agent ratio is as high as 2.1. In Comparative Examples 4 and 5, a chelating agent is added to the hydrogel, but the chelating agent ratio is 1.9 to 2.0. It is presumed that this is because the concentration of the added chelating agent solution is too high.
[0306] Here, when the color tones after the coloring promotion test of Example 2 (addition of chelating agent monomer), Example 5 (addition of chelating agent hydrogel) and Comparative Example 7 (addition of chelating agent during surface crosslinking) are compared, it can be seen that Examples 2 and 5 having chelating agent ratios in the range of 0.8 to 1.8 have less coloring than Comparative Example 7 having a chelating agent ratio of 2.0. That is, it is shown that the chelating agent ratio is preferably 0.8 to 1.8 for color stability.
[0307] [Example 21]
[0308] (Step of Preparing Monomer Aqueous Solution)
[0309] In a polypropylene container having a capacity of 5 L and an inner diameter of 175 mm, a solution (A) obtained by adding a 10 mass % aqueous solution of polyethylene glycol diacrylate (9.19 g, 0.01 mol % relative to acrylic acid) and an aqueous solution of sodium salt of diethylenetriamine pentaacetic acid (7.74 g) as a chelating agent to acrylic acid (1258 g) and a solution (B) obtained by diluting a 48.5 mass % aqueous solution of sodium hydroxide (1058 g) with deionized water (1245 g) were prepared. The solution (A) was stirred with a magnetic stirrer while the solution (B) was added and mixed to prepare a solution (C). It should be noted that the temperature of the solution (C) rose to 82° C. due to the heat of neutralization and heat of solution generated during the mixing process.
[0310] Thereafter, the solution (C) was stirred continuously, and when the temperature of the solution (C) reached 80° C., a 10% by mass sodium persulfate aqueous solution (22.3 g, 0.055 mol % relative to acrylic acid (sodium), 0.13 g / mol) was added to the solution (C) as a polymerization initiator, and stirred for about 3 seconds to prepare a monomer aqueous solution (2). It should be noted that the chelating agent content of the monomer aqueous solution (2) when converted to the acid form was 856 ppm (relative to the monomer).
[0311] (Polymerization process)
[0312] The neutralization rate of the monomer aqueous solution (2) is 73 mol% and the monomer concentration is 43% by mass. Next, the monomer aqueous solution (2) is flowed into a barrel-shaped container in an atmosphere-open system. It should be noted that the barrel-shaped container is a container with a bottom size of 520 mm×520 mm, a top size of 940 mm×940 mm, a height of 300 mm, a trapezoidal central cross section, and a Teflon (registered trademark) sheet attached to the inner surface. In addition, the barrel-shaped container is placed on a heating plate heated to 100°C and preheated. After the monomer aqueous solution (2) is flowed into the barrel-shaped container, the polymerization reaction starts after about 45 seconds, and the monomer aqueous solution heats up. The polymerization start temperature is 78°C. After the monomer aqueous solution (2) generates water vapor and expands and foams in all directions upward, the resulting water-containing gel (2) shrinks to a size slightly larger than the bottom of the barrel-shaped container and ends. It should be noted that the polymerization reaction (expansion and contraction) was completed within about 1 minute, and the state of the hydrogel (2) was maintained in the barrel-shaped container for the next 1.5 minutes. The hydrogel (2) containing bubbles was obtained by the polymerization reaction. The polymerization time was 2.5 minutes.
[0313] (Gel crushing process)
[0314] Next, the hydrogel (2) obtained in the above polymerization reaction was divided into 25 equal parts and supplied to a screw extruder to grind the gel. As the screw extruder, a meat grinder having a porous plate with a diameter of 100 mm, a hole diameter of 9.5 mm, 31 holes, and a thickness of 10 mm at the front end and an outer diameter of the screw shaft of 86 mm was used. While the screw shaft speed of the meat grinder was set to 115 rpm, the hydrogel (2) was supplied at 4640 g / min, and steam was supplied at 108 g / min so that a 0.2 mass % sodium hydrogen sulfite aqueous solution was 100 ppm based on the solid content of the hydrogel.
[0315] The weight average particle size (D50) of the granular hydrogel (2) obtained in the above gel pulverization was 3.0 mm.
[0316] (Drying process)
[0317] Next, 1 kg of the granular hydrogel (2) was spread on a metal net with a mesh size of 300 μm (50 mesh) and placed in a static drying machine. At this time, the layer height of the granular hydrogel stacked in the static drying machine was measured at 5 locations and the average was 5 cm.
[0318] On the other hand, the timing of adding the inorganic reducing agent in the gel pulverization step was determined in advance, and 190°C hot air ventilation was started 5 minutes after the addition of the inorganic reducing agent. It was confirmed that the temperature of the water-containing gel immediately after the gel pulverization was 50°C.
[0319] In the same drying, by repeatedly taking out the semi-dried product from the dryer and measuring the mass, it was found that the solid content reached 80% by mass in 10 minutes.
[0320] After 30 minutes had passed since the start of the hot air ventilation, the hot air ventilation was terminated to obtain a granular dry polymer (2). At this time, the dry polymer had a solid content of 95% by mass.
[0321] (Crushing and classification process)
[0322] Next, the dried polymer (2) was charged into a roll mill (WML type roll mill, manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified by a shaker classifier using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm, thereby obtaining an irregularly shaped crushed water-absorbent resin (2).
[0323] (Surface cross-linking process)
[0324] Next, a surface crosslinking agent solution (1) containing ethylene glycol diglycidyl ether (0.05 parts by mass), propylene glycol (1 part by mass), deionized water (3.0 parts by mass) and isopropyl alcohol (1 part by mass) was added to the irregularly shaped crushed water-absorbent resin (2) (100 parts by mass) and mixed with a spatula until uniform, thereby obtaining a wetted mixture (2). Next, the wetted mixture (2) was uniformly poured into a stainless steel container (width about 22 cm, depth about 28 cm, height about 5 cm), and heated at 100°C for 40 minutes to obtain a surface-crosslinked water-absorbent resin (2).
[0325] Thereafter, the surface-crosslinked water-absorbing resin (2) was passed through a JIS standard sieve having an opening of 850 μm to obtain a particulate water-absorbing agent (21) as a final product. The results are shown in the following table.
[0326] [Examples 22 to 41]
[0327] In Example 21, except that the preparation of the monomer aqueous solution, the chemical reagent (chelating agent) used therein, and the inorganic reducing agent added in the gel grinding step were changed to the values shown in the table, particulate water-absorbing agents (22 to 41) were produced in the same manner as in Example 21. The results are shown in the following table.
[0328] [Table 7]
[0329]
[0330] [Table 8]
[0331]
[0332] [Table 9]
[0333]
[0334] [Table 10]
[0335]
[0336] [Table 11]
[0337]
[0338] [Table 12]
[0339]
[0340] [Table 13]
[0341]
[0342] [Table 14]
[0343]
[0344] 〔Investigation〕
[0345] In Examples 21 to 41, the same tendency as in Examples 1 to 20 was observed.
[0346] [Example 42]
[0347] To 100 parts by mass of the particulate water-absorbing agent (22) of Example 22, 1 part by mass of a 10% by mass sodium sulfite aqueous solution was added, mixed with a spatula until uniform, and then uniformly placed in a stainless steel container (width about 22 cm, depth about 28 cm, height about 5 cm), and heated at 80° C. for 30 minutes. Thereafter, the mixture was passed through a JIS standard sieve with a mesh size of 850 μm, thereby obtaining a particulate water-absorbing agent (42) as a final product. The chelating agent ratio was 1.0, which was the same as that of the particulate water-absorbing agent (22). The initial color tone YI of the particulate water-absorbing agent (42) was 11.1, the residual monomer was 345 ppm, and the reducing agent concentration was 980 ppm.
[0348] [Example 43]
[0349] The particulate water-absorbing agent (42) of Example 42 was mixed with hydrotalcite (product name DHT-6, manufactured by Kyowa Chemical Industry Co., Ltd., Mg6A l2 (OH) 16 0.3 parts by mass of CO3·4H2O [x=0.25, m=0.50 in the general formula (1)], volume average particle size of 0.5 μm] was added to obtain a particulate water absorbing agent (43) as a final product. 30 g of the water absorbing resin and hydrotalcite were put into a 225 mL mayonnaise bottle and mixed by vibration with a paint stirrer (product No. 488 test disperser / manufactured by Toyo Seiki Seisaku-sho) at 800 (cycle / min) (CPM) for 3 minutes. The initial color tone YI of the particulate water absorbing agent (43) was 9.5.
[0350] [Example 44]
[0351] A particulate water absorbing agent (44) as a final product was obtained in the same manner as in Example 43 except that 0.3 parts by weight of AEROSIL (trademark) 200 as fumed silica was added instead of 0.3 parts by weight of hydrotalcite. The initial color tone YI of the particulate water absorbing agent (44) was 10.6.
[0352] 〔Investigation〕
[0353] The particulate water absorbing agent (43) to which hydrotalcite having a volume average particle size of 0.5 μm was added had an improved initial color tone YI compared to the particulate water absorbing agent (42) and the particulate water absorbing agent (44).
[0354] This application is based on Japanese patent application No. 2019-204870 filed on November 12, 2019, the disclosure of which is incorporated herein by reference in its entirety.
Claims
1. A particulate water-absorbing agent comprising a poly(meth)acrylic acid (salt)-based water-absorbing resin as a main component, the particulate water-absorbing agent comprising a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom, The chelating agent ratio of the particulate water-absorbing agent calculated according to the following steps (a) to (c) is 0.8 to 1.2, (a) subjecting the particulate water absorbing agent to a predetermined impact test, wherein 30 g of the particulate water absorbing agent and 10 g of glass beads having a diameter of 6 mm are placed in a glass container having a diameter of 6 cm and a height of 11 cm, and the particulate water absorbing agent is crushed using a paint shaker, wherein the crushing is performed by shaking the paint shaker at 800 cycles / min for 30 minutes, and after the shaking, the glass beads are removed using a JIS standard sieve having a mesh size of 2 mm; (b) using a JIS standard sieve, the particulate water-absorbing agent subjected to the impact test is sieved into a particle group 1 having a particle size of less than 300 μm and a particle group 2 having a particle size of 300 μm or more and less than 850 μm; (c) After quantifying the content C1 of the chelating agent in the particle group 1 and the content C2 of the chelating agent in the particle group 2, C1 is divided by C2.
2. The particulate water-absorbing agent according to claim 1, wherein The chelating agent ratio is 0.8 to 1.
1.
3. The particulate water-absorbing agent according to claim 1, wherein The hue YI in the initial hue test was 12 or less.
4. The particulate water-absorbing agent according to claim 1, wherein The hue YI in the initial hue test was 10 or less.
5. The particulate water-absorbing agent according to claim 1, wherein The hue YI in the initial hue test was 8 or less.
6. The particulate water-absorbing agent according to claim 1, wherein The hue YI in the initial hue test was 6 or less.
7. The particulate water-absorbing agent according to claim 1, wherein The hue YI in the initial hue test was 4 or less.
8. The particulate water-absorbing agent according to claim 1, wherein The hue YI in the initial hue test was 2 or less.
9. The particulate water-absorbing agent according to claim 1, wherein The content C7 of the chelating agent in the particulate water-absorbing agent is 10 to 5000 ppm.
10. The particulate water-absorbing agent according to claim 1, wherein The content C7 of the chelating agent in the particulate water-absorbing agent is 100 to 5000 ppm.
11. The particulate water-absorbing agent according to claim 1, wherein The content C7 of the chelating agent in the particulate water-absorbing agent is 200 to 3000 ppm.
12. The particulate water-absorbing agent according to claim 1, wherein The content C7 of the chelating agent in the particulate water-absorbing agent is 500 to 2000 ppm.
13. The particulate water-absorbing agent according to claim 1, wherein The chelating agent is at least one compound selected from the group consisting of amino polycarboxylic acids and amino polyphosphoric acids.
14. The particulate water-absorbing agent according to claim 1, wherein The chelating agent is at least one compound selected from the group consisting of diethylenetriaminepentaacetic acid, ethylenediaminetetrakis(methylenephosphonic acid) and salts thereof.
15. The particulate water-absorbing agent according to claim 1, wherein The chelating agent is diethylenetriaminepentaacetic acid or its salt.
16. The particulate water-absorbing agent according to claim 1, wherein The inorganic reducing agent is sulfite or bisulfite.
17. The particulate water-absorbing agent according to claim 1, wherein the residual ratio of the chelating agent is 50% by mass or more.
18. The particulate water-absorbing agent according to claim 1, wherein The residual rate of the chelating agent is 55% by mass or more.
19. The particulate water-absorbing agent according to claim 1, wherein The residual rate of the chelating agent is 60% by mass or more.
20. The particulate water-absorbing agent according to claim 1, wherein The residual rate of the chelating agent is 65% by mass or more.
21. The particulate water-absorbing agent according to claim 1, wherein The residual rate of the chelating agent is 70% by mass or more.
22. The particulate water-absorbing agent according to claim 1, wherein The chelating agent residual rate is 75% by mass or more.
23. The particulate water-absorbing agent according to claim 1, wherein The residual rate of the chelating agent is 80% by mass or more.
24. The particulate water-absorbing agent according to claim 1, wherein The residual rate of the chelating agent is 85% by mass or more.
25. The particulate water-absorbing agent according to claim 1, wherein the residual monomer content is 700 ppm or less.
26. The particulate water-absorbing agent according to claim 1, wherein The content of residual monomers was 500 ppm or less.
27. The particulate water-absorbing agent according to claim 1, wherein The content of residual monomers was 300 ppm or less.
28. The particulate water-absorbing agent according to claim 1, wherein The content of the inorganic reducing agent is 1 to 3000 ppm.
29. The particulate water-absorbing agent according to claim 1, wherein The content of the inorganic reducing agent is 10 to 3000 ppm.
30. The particulate water-absorbing agent according to claim 1, wherein The content of the inorganic reducing agent is 12 to 2000 ppm.
31. The particulate water-absorbing agent according to claim 1, wherein The proportion of particles having a particle size of less than 850 μm is 90 to 100% by mass based on the entirety.
32. The particulate water-absorbing agent according to claim 1, wherein The mass ratio of particles having a particle size of less than 300 μm to particles having a particle size of 300 μm or more and less than 850 μm is 70:30 to 10:
90.
33. The particulate water-absorbing agent according to claim 1, wherein The mass ratio of the particles with a particle size less than 300 μm to the particles with a particle size of 300 μm or more and less than 850 μm is 60:40 to 15:
85.
34. The particulate water-absorbing agent according to claim 1, wherein The mass ratio of the particles having a particle size of less than 300 μm to the particles having a particle size of 300 μm or more and less than 850 μm is 50:50 to 20:
80.
35. The particulate water-absorbing agent according to claim 1, wherein The mass ratio of the particles having a particle size less than 300 μm to the particles having a particle size of 300 μm or more and less than 850 μm is 40:60 to 25:
75.
36. The particulate water-absorbing agent according to claim 1, wherein The proportion of particles having a particle size of 150 μm or more and less than 850 μm as defined by a JIS standard sieve is 90% by mass or more.
37. The particulate water-absorbing agent according to claim 1, wherein The proportion of particles having a particle size of 150 μm or more and less than 850 μm as defined by a JIS standard sieve is 95% by mass or more.
38. The particulate water-absorbing agent according to claim 1, wherein The proportion of particles having a particle size of 150 μm or more and less than 850 μm as defined by the JIS standard sieve is 98% by mass or more.
39. The particulate water-absorbing agent according to claim 1, wherein water-insoluble inorganic fine particles having a volume average particle size of 0.2 to 3 μm are added to the surface of the particles. The particulate water-absorbing agent according to claim 1 , comprising silicon dioxide. The particulate water-absorbing agent according to claim 1 , comprising hydrotalcite.
42. The particulate water-absorbing agent according to claim 1, wherein Add hydrotalcite to the particle surface.
43. A method for producing a granular water-absorbing agent, wherein: The particulate water absorbing agent has a poly(meth)acrylic acid (salt)-based water absorbing resin as a main component, and contains a chelating agent having a nitrogen atom and an inorganic reducing agent having a sulfur atom. The production method comprises the step of adjusting the ratio of the chelating agent according to claim 1 to 0.8 to 1.
2.
44. A method for producing a granular water-absorbing agent, comprising the following steps: A process for preparing a monomer aqueous solution containing (meth)acrylic acid (salt) and persulfate (salt); A polymerization step of polymerizing the monomers contained in the monomer aqueous solution to obtain a hydrogel; A gel pulverizing step of pulverizing the hydrogel to obtain a granular hydrogel; A drying step of drying the particulate aqueous gel to obtain a dry polymer; a step of pulverizing or classifying the dry polymer to obtain a water-absorbent resin powder; and a surface crosslinking step of crosslinking the surface of the water-absorbent resin powder to obtain water-absorbent resin particles, The manufacturing method comprises the following steps: (i) adding a chelating agent having a nitrogen atom in an amount of 10 to 5000 ppm based on the mass of the monomers as the monomer component to the aqueous monomer solution, The manufacturing method comprises the following steps: (iii) adding to the hydrogel or the particulate hydrogel an inorganic reducing agent having a sulfur atom in an amount of 10 to 50,000 ppm by mass based on the solid content of the hydrogel or the particulate hydrogel; The inorganic reducing agent is in the form of a 0.01 to 20 mass % aqueous solution. The step of adding the inorganic reducing agent is a step of kneading the inorganic reducing agent while pulverizing the hydrogel in the gel pulverizing step.
45. The manufacturing method according to claim 44, wherein: The particulate water-absorbing agent is obtained by polymerizing monomers of an aqueous monomer solution containing a chelating agent having a nitrogen atom. The amount C3 of the chelating agent added to the monomer aqueous solution relative to the monomer solid content is 50% by mass or more relative to the total amount C5 of the chelating agent added in the production process of the particulate water-absorbing agent, The content C6 of the chelating agent relative to the solid content of the particulate water-absorbing agent is 50% by mass or more of the above C5.
46. The manufacturing method according to claim 45, wherein: The C3 accounts for 60 mass % or more of the C5.
47. The manufacturing method according to claim 45, wherein: The C3 accounts for 70 mass % or more of the C5.
48. The manufacturing method according to claim 45, wherein: The C3 accounts for 80 mass % or more of the C5.
49. The manufacturing method according to claim 45, wherein: The C3 accounts for 90 mass % or more of the C5.
50. The manufacturing method according to claim 44, wherein: The particulate water-absorbing agent is obtained by adding a chelating agent having a nitrogen atom to the hydrogel or the particulate hydrogel obtained by pulverizing the hydrogel, wherein the hydrogel is obtained by polymerizing a monomer in a monomer aqueous solution. The amount C4 of the chelating agent added to the hydrogel or the particulate hydrogel is 50% by mass or more relative to the total amount C5 of the chelating agent added in the production process of the particulate water-absorbing agent, The content C6 of the chelating agent relative to the solid content of the particulate water-absorbing agent is 50% by mass or more of the above C5.
51. The manufacturing method according to claim 50, wherein: The C4 accounts for 70 mass % or more of the C5.
52. The manufacturing method according to claim 50, wherein: The C4 accounts for 80 mass % or more of the C5.
53. The manufacturing method according to claim 50, wherein: The C4 accounts for 90 mass % or more of the C5.
54. The manufacturing method according to claim 44, wherein: The polymerization time for polymerizing the monomers contained in the aqueous monomer solution is 30 minutes or less.
55. The manufacturing method according to claim 54, wherein: The polymerization time is less than 10 minutes.
56. The manufacturing method according to claim 44, wherein: In the drying step, drying is performed using hot air at 120 to 250°C.
57. The manufacturing method according to claim 44, wherein: In the drying step, the time required for drying until the solid content of the dry polymer reaches 80% by mass is 30 minutes or less.
58. The manufacturing method according to claim 44, wherein: In the drying step, the drying is performed using a dryer selected from a static dryer and a belt dryer.
59. The manufacturing method according to claim 58, wherein: The layer height of the hydrogel or the particulate hydrogel stacked in the dryer is 1 to 10 cm.
60. The manufacturing method according to claim 44, wherein: The time from the addition of the inorganic reducing agent to the start of drying is 30 minutes or less, or the temperature of the water-containing gel from the addition of the inorganic reducing agent to the start of drying is 0 to 55°C.
61. The manufacturing method according to claim 44, wherein: While the aqueous gel is being pulverized, the chelating agent is added.
62. The manufacturing method according to claim 44, wherein: The persulfate (salt) is added in an amount of 0.02 mol % or more relative to the monomer.
63. The manufacturing method according to claim 44, wherein: In the step of preparing the aqueous monomer solution containing (meth)acrylic acid (salt) and persulfate (salt), (meth)acrylic acid (salt) as a monomer and an alkaline substance for neutralizing the monomer are mixed with the persulfate (salt) when the temperature of the solution obtained by mixing the (meth)acrylic acid (salt) as a monomer and the alkaline substance for neutralizing the monomer is 50 to 102°C.
64. The manufacturing method according to claim 44, wherein: Water-insoluble inorganic fine particles having a volume average particle size of 0.2 to 3 μm are added to the particulate water-absorbing agent.
65. A water-absorbing article comprising the particulate water-absorbing agent according to any one of claims 1 to 42 or the particulate water-absorbing agent obtained by the production method according to any one of claims 43 to 64.
Citation Information
Patent Citations
Water-absorbing agent, its production and production apparatus therefor
JP1997235378A
Manufacturing method of water-absorbable resin
JP2003206305A
Water-absorbing resin composition
JP2005029751A
Solar cell element and method for manufacturing solar cell element
JP2019204870A
Method for continuous production of water-absorbent resin
US20050215734A1